Electrode base material, electrode base material laminate, electrode, secondary battery, and method for manufacturing the same

JP2025030898APending Publication Date: 2025-03-07CANON KK
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023136586
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-24
Publication Date
2025-03-07

AI Technical Summary

Benefits of technology

【0016】 本開示の少なくとも一つの態様によれば、電子伝導性及びイオン伝導性に優れ、内部抵抗が低く出力の高い二次電池を製造することができる電極基材、電極及び二次電池、並びに、電極基材、電極及び二次電池の製造方法が提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025030898000001_ABST
    Figure 2025030898000001_ABST
Patent Text Reader

Abstract

To provide: an electrode base material for secondary batteries with which a secondary battery that has a low internal resistance can be manufactured; an electrode base material laminate; an electrode; the secondary battery; and methods for manufacturing the same.SOLUTION: There is provided an electrode base material used for manufacturing an electrode. The electrode base material includes: a resin base material; and active material particles and solid electrolyte particles on the resin base material. A particle layer which contains the active material particles and the solid electrolyte particles is formed on the resin base material. When the particle layer is viewed through from a surface side on the resin base material side or from the reverse surface side, the solid electrolyte particles are disposed so as to cover at least a part of the surfaces of the active material particles. In a cross-sectional observation of the particle layer, the difference between the area ratio of exposed surfaces of the active material particles on a surface of the particle layer on the side in contact with the resin base material, and the area ratio of exposed surfaces of the active material particles on the reverse surface of the particle layer on the side in contact with the resin base material is 1 to 70 area%.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an electrode substrate, an electrode substrate laminate, an electrode and a secondary battery, and a method for producing the same. [Background technology]

[0002] In general, secondary batteries are composed of electrodes (positive and negative electrodes) and an electrolyte, and are charged and discharged by the movement of ions between the electrodes via the electrolyte. Such secondary batteries are used in a wide range of applications, from small devices such as mobile phones to large devices such as electric vehicles. Therefore, there is a demand for further improvement in the performance of secondary batteries.

[0003] In recent years, research and development of so-called all-solid-state batteries, which use inorganic solid electrolytes as the electrolyte, has progressed. All-solid-state batteries are expected to improve the safety and increase the capacity and power output of secondary batteries by replacing conventional organic electrolytes with solid electrolytes. On the other hand, in all-solid-state batteries, both the active material and the solid electrolyte are solid, and solid particles form interfaces with each other, resulting in high interface resistance. As a result, the resistance inside the electrode increases, and the resulting battery output decreases. Therefore, technologies have been developed to reduce the internal resistance.

[0004] Patent Document 1 discloses an electrode in which active material particles and solid electrolyte particles are arranged in a pattern to facilitate smooth ion conduction between the active material and the solid electrolyte. Patent Document 2 discloses an electrode in which the concentration of active material particles is increased and the concentration of solid electrolyte particles is decreased on the current collector side, while the concentration of active material is decreased and the concentration of solid electrolyte particles is increased on the solid electrolyte layer side, thereby ensuring smooth ion conduction. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2019-137060 A [Patent Document 2] Patent Publication No. 2021-039848 Summary of the Invention [Problem to be solved by the invention]

[0006] However, according to the study by the present inventors, since the solid electrolyte is not suitable for electronic conduction and the active material is not suitable for ionic conduction, it has been found that the contact between the particles is insufficient and the internal resistance cannot be sufficiently reduced by simply controlling the arrangement of each particle as in Patent Document 1. In addition, as in Patent Document 2, when the concentration of each particle is graded in the electrode, the contact between the same type of particles is insufficient between the low concentration region and the high concentration region, which results in a portion where the ion conduction path or the electron conduction path is not connected, and the internal resistance cannot be sufficiently reduced. Therefore, it has been found that it is necessary to further reduce the internal resistance of the electrode and further improve the output of the secondary battery.

[0007] Accordingly, an object of the present disclosure is to provide an electrode substrate for a secondary battery, an electrode substrate laminate, an electrode, and a secondary battery, which are capable of producing a secondary battery having excellent electronic conductivity and ionic conductivity, low internal resistance, and high output, as well as methods for producing the electrode substrate, the electrode substrate laminate, the electrode, and the secondary battery. [Means for solving the problem]

[0008] According to at least one aspect of the present disclosure, An electrode substrate used in the manufacture of an electrode, The electrode substrate is A resin substrate, and active material particles and solid electrolyte particles on the resin substrate, a particle layer including the active material particles and the solid electrolyte particles is formed on the resin substrate; the solid electrolyte particles are arranged so as to cover at least a part of the surface of the active material particles when the particle layer is viewed through from the surface side in contact with the resin substrate or the surface side opposite to the surface in contact with the resin substrate, In cross-sectional observation of the particle layer using a scanning electron microscope (SEM), an area ratio of the exposed surface of the active material particles to a surface of the particle layer on the side in contact with the resin substrate; and The electrode base material is characterized in that the difference between the area ratio of the exposed surface of the active material particles on the surface opposite to the side in contact with the resin base material of the particle layer is 1 to 70 area %.

[0009] According to at least one embodiment of the present disclosure, there is provided an electrode substrate laminate in which a plurality of the above-described electrode substrates are laminated.

[0010] According to at least one aspect of the present disclosure, there is provided an electrode for a secondary battery, the electrode being a sintered body of the electrode base material described above. Also, there is provided an electrode being a sintered body of an electrode base material laminate in which a plurality of the electrode base materials are laminated.

[0011] According to at least one embodiment of the present disclosure, there is provided a secondary battery comprising an electrode that is a sintered body of the electrode base material described above, and an electrolyte layer adjacent to the electrode.

[0012] According to at least one aspect of the present disclosure, A method for producing the electrode base material used in the production of an electrode, comprising the steps of: The production method comprises the steps of: preparing the resin substrate having an adhesive portion; disposing the active material particles on a surface of the adhesive portion; a step of rubbing the surfaces of the active material particles arranged on the surface of the adhesive portion; disposing the solid electrolyte particles on the surface of the adhesion portion and the rubbed surfaces of the active material particles; A method for producing an electrode substrate having the following structure is provided.

[0013] According to at least one aspect of the present disclosure, A method for producing an electrode substrate used in the production of an electrode, comprising the steps of: The electrode substrate is A resin substrate, and active material particles and solid electrolyte particles on the resin substrate, a particle layer including the active material particles and the solid electrolyte particles is formed on the resin substrate; the solid electrolyte particles are arranged so as to cover at least a part of the surface of the active material particles when the particle layer is viewed through from the surface side in contact with the resin substrate or the surface side opposite to the surface in contact with the resin substrate, The production method comprises the steps of: preparing the resin substrate having an adhesive portion; disposing the active material particles on a surface of the adhesive portion; a step of rubbing the surface of the active material particles disposed on the surface of the adhesive portion; disposing the solid electrolyte particles on the surface of the adhesive portion and the rubbed surfaces of the active material particles; A method for producing an electrode substrate having the following structure is provided.

[0014] According to at least one aspect of the present disclosure, there is provided a method for producing an electrode, comprising the steps of: A step of laminating a plurality of the electrode base materials to form a laminate; removing the resin substrate from the laminate to obtain a three-dimensional object; and applying pressure to the three-dimensional object to obtain an electrode.

[0015] Furthermore, according to at least one aspect of the present disclosure, there is provided a method for producing a secondary battery, comprising the steps of: The production method comprises the steps of: preparing an electrode by the electrode manufacturing method; and laminating the electrode, the current collector, and the electrolyte. Effect of the Invention

[0016] According to at least one aspect of the present disclosure, there are provided an electrode substrate, an electrode, and a secondary battery capable of producing a secondary battery having excellent electronic conductivity and ionic conductivity, low internal resistance, and high output, and methods for producing the electrode substrate, the electrode, and the secondary battery. [Brief description of the drawings]

[0017] [Figure 1] FIG. 2 is a conceptual diagram showing an electrode substrate. [Diagram 2] 1 is a conceptual diagram showing a manufacturing method of an electrode substrate. [Diagram 3] FIG. 1 is a diagram showing a schematic configuration of a particle arrangement device 1. [Figure 4] FIG. 2 is a diagram showing a schematic configuration of a filling device. [Diagram 5] FIG. 2 is a schematic diagram of a filler being carried on a first substrate. [Figure 6] FIG. 2 is an enlarged view of the vicinity of the surface of the first substrate. [Figure 7] FIG. 13 is a diagram showing a schematic configuration of a filling device when brush fibers are used as a support material. [Figure 8] FIG. 2 is a diagram illustrating a configuration of a transfer unit. [Figure 9] 13 is an enlarged view of the vicinity of the surface of a second substrate during a filling process using a second filling device. [Figure 10] FIG. 2 is a diagram showing a schematic view of a second substrate after first particles P1 and second particles P2 have been transferred. [Figure 11] FIG. 2 is a diagram showing a schematic configuration of a particle arrangement device 2. [Figure 12] FIG. 2 is a schematic diagram showing the devices for the second and third steps in the manufacturing method of the electrode substrate. [Figure 13] FIG. 13 is a schematic diagram showing a third filling device that does not use a belt device. [Figure 14] FIG. 4 is a schematic diagram illustrating the operation of the filling device. [Figure 15] FIG. 1 is an image diagram showing a method for manufacturing an electrode. [Figure 16] FIG. 2 is a diagram showing a schematic configuration of a laminate forming apparatus. [Figure 17] FIG. 2 is a diagram showing a schematic configuration of a sintering treatment apparatus. [Figure 18] SEM images of laminates and three-dimensional objects at each stage of the electrode manufacturing method. [Figure 19] FIG. 1 is a diagram illustrating an overall configuration of an additive manufacturing system. [Figure 20] 1 is a conceptual diagram showing a manufacturing method of an electrode substrate. [Figure 21]FIG. 2 is a diagram showing a schematic structure of a first base material having a concave-convex pattern formed on its surface. [Figure 22] 1 is an SEM image of the electrode substrate of Example 1. [Figure 23] FIG. 2 is a diagram showing an example of an SEM image of the upper surface of an electrode substrate, the image being used to calculate the coverage ratio. [Figure 24] FIG. 4 is a diagram showing an example of a cross-sectional image of an electrode substrate photographed by an electron microscope. [Diagram 25] 5A and 5B are diagrams showing examples of images used for calculating the area of ​​exposed surfaces of active material particles on the surface of a particle layer. [Figure 26] 1 is a BIB-SEM image of a cross section of an electrode produced using the electrode base material of Example 1. [Figure 27] 1A to 1C are schematic cross-sectional views of an electrode substrate laminate and an electrode produced using the electrode substrate laminate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] In the present disclosure, the expressions "XX to YY" and "XX to YY" expressing a numerical range mean a numerical range including the lower and upper limits, unless otherwise specified. When a numerical range is described in stages, any combination of the upper and lower limits of each numerical range is also disclosed.

[0019] When an inorganic solid electrolyte is used as the electrolyte, the active material and the electrolyte are in contact with each other in a solid state, so it is difficult to obtain a sufficient contact area, and it is difficult to form a conductive path at the interface. In particular, if the active material aggregates, the aggregated active material has even less contact with the solid electrolyte, and the ion conductivity is likely to decrease. This may increase the internal resistance of the battery and lead to a decrease in battery output.

[0020] In order to solve the above problems, the present inventors conducted detailed studies on the arrangement of active material particles and solid electrolyte particles inside an electrode. As a result of the studies, it was found that both electronic conductivity and ionic conductivity can be improved by arranging the active material particles on the electrode surface so that the solid electrolyte particles cover at least a part of the surface of the active material particles and controlling the area ratio of the exposed surface of the active material particles. Specifically, both electronic conductivity and ionic conductivity can be improved by setting the difference between the area ratio of the active material particles exposed on one surface of the electrode and the area ratio of the active material particles exposed on the other surface to 1 to 70 area %. This means that a large area of ​​the active material particles is exposed on one surface of the electrode, while a part of the surface of the active material particles is covered by solid electrolyte particles on the other surface, reducing the area ratio of the exposed surface of the active material particles.

[0021] In the present disclosure, the above-mentioned embodiment is realized by using an electrode substrate in which active material particles and solid electrolyte particles are disposed on a resin substrate having the characteristics of the present disclosure. A plurality of electrode substrates can be laminated to form an electrode substrate laminate. The electrode substrate and the electrode substrate laminate can also be used as materials for electrodes.

[0022] In a secondary battery manufactured using an electrode having such a configuration, a large amount of active material particles are exposed on one side of the electrode, which increases the contact area between the active material having excellent electronic conductivity and the current collector, thereby smoothing the electron transfer. In addition, on the side opposite to the above side of the electrode, the exposed area of ​​the surface of the active material particles is reduced, which increases the contact area between the solid electrolyte particles and smooths ion conduction. Smooth electronic and ionic conduction reduces the internal resistance of the electrode, thereby improving the output of the secondary battery.

[0023] In order to prepare an electrode having the above-mentioned configuration, it is important to control the arrangement of the active material particles and solid electrolyte particles in the electrode substrate. Specifically, the solid electrolyte particles are arranged on the surface of the electrode substrate so that they cover at least a part of the surface of the active material particles. In addition, the solid electrolyte particles are arranged so as to be unevenly distributed in the thickness direction of the electrode substrate. By arranging the active material particles and solid electrolyte particles in this manner, the active material particles can be arranged so that the area ratio of the surface of the active material particles exposed on one surface of the electrode substrate is sufficiently larger than the area ratio of the surface of the active material particles exposed on the other surface. As a result, an electrode substrate having excellent electronic conductivity and ionic conductivity can be obtained.

[0024] By manufacturing an electrode using the electrode base material having the above-mentioned configuration, it is possible to improve electronic conduction between active material particles in the electrode, electronic conduction from the active material particles to the current collector, and ionic conduction from the active material particles to the electrolyte. Furthermore, in a secondary battery using such an electrode, the internal resistance is reduced and the output is improved.

[0025] In this disclosure, electronic conductivity and ionic conductivity are conveniently referred to as the “rate characteristics” of the prototype battery. " is used as an indicator for evaluation. The electrode substrate, the electrode substrate laminate, the electrode, and the secondary battery using them, as well as the manufacturing method thereof, will be described in detail below.

[0026] The electrode substrate of the present disclosure can be used in the manufacture of electrodes for secondary batteries. Hereinafter, a positive electrode substrate using positive electrode active material particles will be described as an example, but the electrode substrate of the present disclosure can be used for both positive and negative electrodes. The electrode substrate includes a resin substrate, and active material particles and solid electrolyte particles on the resin substrate. A particle layer including the active material particles and the solid electrolyte particles is formed on the resin substrate.

[0027] The resin substrate is a substrate made of a material containing a resin. By using a substrate made of an organic material such as a resin as the substrate, it is possible to easily remove the substrate by heating in the manufacturing process of the electrode substrate described later. The resin contained in the material of the resin substrate is not particularly limited, and examples thereof include polyesters such as polyethylene (PE), polypropylene (PP) and polyethylene terephthalate (PET), as well as polyamides such as nylon. Of these, it is preferable to use PET from the viewpoints of its decomposition temperature and the low toxicity of gases generated during thermal decomposition.

[0028] The active material particles are not particularly limited and may be any known active material. For example, a composite oxide containing lithium may be used. Specific examples include Li-Co oxide active material particles such as LiCoO2, LiMO2 (M is one element selected from the group consisting of Ni, Mn, and Co), Li-PO4 oxide active material particles, Si active material particles (Si, Si-C, etc.), graphite active material particles (graphite, graphene, carbon nanotubes, etc.), lithium vanadium compounds (Li3V2(PO4)3, LiVOPO4), and olivine phosphate compounds (LiMPO4 (M is one or more elements selected from the group consisting of Co, Ni, Mn, Fe, Mg, V, Nb, Ti, Al, and Zr)). Also, a positive electrode active material that does not contain lithium may be used. Specifically, for example, metal oxides (MnO2, V2O5, etc.) and fluorides (FeF3, VF3, etc.) can be mentioned. When using a positive electrode active material that does not contain lithium, it can be used by disposing a lithium-containing metallic lithium or a negative electrode active material doped with lithium ions as the negative electrode active material and starting with discharging.

[0029] The present inventors have revealed that the use of Li-Co oxide-based active material particles among the above positive electrode active material particles increases the surface area of ​​the positive electrode active material particles and improves the output characteristics of the secondary battery (JP Patent Publication No. 2020-198301). In addition, Li-PO4 oxide-based active material particles are very stable because the covalent bond between PO is strong and oxygen release is suppressed. For this reason, it is preferable to include Li-Co oxide-based active material particles and Li-PO4 oxide-based active material particles among the above positive electrode active material particles.

[0030] The active material particles may be a commercially available product, or may be prepared separately as a material. As the Li-Co oxide-based active material particles, for example, Cellseed C-5H (trade name, manufactured by Nippon Chemical Industry Co., Ltd.) (LiCoO2) can be used. As the LiMO2 (M is an element selected from the group consisting of Ni, Mn, and Co), Cellseed NMC (trade name, manufactured by Nippon Chemical Industry Co., Ltd.) (LiNi (1-x-y) Mn x Co y As the Li-PO4 oxide-based active material particles, LiFePO4 (manufactured by Toshima Manufacturing Co., Ltd.) or Li3V2(PO4)3 (manufactured by Tokyo Chemical Industry Co., Ltd.) can be used. In addition, active material particles with low electronic conductivity, such as LiFePO4 and Li3V2(PO4)3, When using the above, the particle surface may be coated with carbon by a general method. The active material particles may be used alone or in combination of two or more kinds.

[0031] The solid electrolyte particles are not particularly limited, and ion-conductive solids that are commonly used in all-solid-state batteries can be used. For example, Li-B oxide-based solid electrolyte particles, Li-Yb oxide-based solid electrolyte particles, Nasicon-type solid electrolyte particles (LiAlTi(PO4)3, LiAlGe(PO4)3, etc.), Perovskite-type oxide-based solid electrolyte particles (Li x La (1-x) / 3 TiO3, Li x La (1-x) / 3 NbO3, etc.), solid electrolyte particles of garnet-type oxides (Li7La3Zr2O 12, etc.), and Li-PO-based solid electrolyte particles (Li3PO4, LiPON (particles in which part of O in Li3PO4 is replaced with N), etc.). Among the above solid electrolyte particles, Li-B oxide-based solid electrolyte particles and Li-Yb oxide-based solid electrolyte particles can be sintered at a relatively low temperature (700° C. or lower), and therefore can suppress reaction with the positive electrode active material particles during sintering and maintain ionic conductivity. For this reason, among the above solid electrolyte particles, it is preferable to include Li-B oxide-based solid electrolyte particles and Li-Yb oxide-based solid electrolyte particles.

[0032] The solid electrolyte particles to be used may be commercially available products, or may be separately prepared as a material. As the Li-B oxide-based solid electrolyte particles, for example, Li3BO3 (manufactured by Toshima Manufacturing Co., Ltd.) or particles in which part of O in Li3BO3 is replaced with C can be used. As the Li-Yb oxide-based solid electrolyte particles, for example, a compound described in JP-A-2022-130301 can be used. For example, Li 5.9 Yb 0.81 La 0.09 Zr 0.1 (BO3)3, etc. can be used. These solid electrolyte particles may be made amorphous in advance by planetary ball milling or the like.

[0033] The surface area ratio of the active material particles exposed on the surface of the particle layer is determined from a two-dimensional image of a cross section obtained by processing the cross section with a broad ion beam (BIB) of Ar and then using a scanning electron microscope. Hereinafter, the above-mentioned method of observing two-dimensional images is called BIB-SEM. The details of the measurement method will be described later.

[0034] The electrode base material has a particle layer including active material particles and solid electrolyte particles formed on a resin base material. When the particle layer is viewed through from the surface side in contact with the resin base material or the surface side opposite to the surface side in contact with the resin base material, the solid electrolyte particles are arranged so as to cover at least a part of the surface of the active material particles. By arranging in this manner, a uniform dense portion of the active material particles and the solid electrolyte particles is provided, and the active material particles and the solid electrolyte particles can be sufficiently contacted with each other. As a result, the ion conductivity can be improved.

[0035] The active material particles are preferably arranged at the same height on the resin substrate. Whether the active material particles are provided at the same height can be determined from the above-mentioned cross-sectional SEM image. In the present disclosure, the height of the active material particles refers to the height from the surface of the resin substrate on which the active material particles are arranged to the position of the uppermost surface of the active material particles. The height of the active material particles can be measured by the method described later. The active material particles may be arranged so as to have projections and recesses, but the height of the projections is preferably three times or less the average height of the active material particles. The height of the projections is the height of the active material particles having the highest height among the active material particles in the cross-sectional SEM image. The average height of the active material particles is determined by dividing the cross-sectional SEM image into rows of one pixel in width, determining the height of the active material particles from the surface of the resin substrate in each row, and averaging the heights of the active material particles in all rows. The average height of the active material particles can be measured by the method described below. By having the height of the projections be three times or less the average height of the active material particles, the arrangement density of the active material particles becomes uniform, and there is no contact between the active material particles or the active material particles are prevented from moving. This allows sufficient contact between the porous particles and the solid electrolyte particles.

[0036] The resin substrate may have regions where no active material particles are disposed, and other particles, such as solid electrolyte particles or graphite particles, are disposed in these regions. The average height of the active material particles from the surface of the resin substrate is preferably 1 to 50 μm, more preferably 2 to 10 μm. If the average height is less than 1 μm, it is difficult to uniformly arrange the active material particles on the resin substrate. Therefore, it is difficult to smoothly conduct electronic and ionic conduction. On the other hand, if the average height is greater than 50 μm when using small-diameter active material particles (up to 10 μm), the active material particles will be stacked over the entire region and arranged in a multi-layered manner, making it difficult to connect the paths of electronic and ionic conduction inside. If the average height is greater than 50 μm when using large-diameter active material particles (10 μm or more), the gaps between the particles will be large, making it difficult to smoothly conduct electronic and ionic conduction. In other words, by setting the average height of the active material particles from the surface of the resin substrate to 1 to 50 μm, it is possible to effectively control the paths of electronic and ionic conduction. The active material particles may be arranged on the resin substrate so that a plurality of active material particles are stacked on top of each other. When the active material particles are arranged so as to be stacked, the maximum height of the active material particles can be appropriately adjusted depending on the particle size, etc., but is preferably, for example, about 1 to 10 times the average particle size of the active material particles.

[0037] In cross-sectional observation of the particle layer of the electrode substrate by a scanning electron microscope (SEM), the difference between the area ratio of the exposed surface of the active material particles on the surface of the particle layer that comes into contact with the resin substrate and the area ratio of the exposed surface of the active material particles on the surface of the particle layer opposite to the side that comes into contact with the resin substrate is 1 to 70 area %. That is, the electrode base material of the present disclosure has a configuration in which the area ratio of the surface of the active material particles exposed on one surface of the particle layer is significantly different from the area ratio of the surface of the active material particles exposed on the other surface of the particle layer. The area ratio of the surface of the active material particles exposed on the surface of the particle layer and the difference can be calculated by the method described later.

[0038] The difference between the area ratio of the exposed surface of the active material particles on the surface of the particle layer in contact with the resin substrate and the area ratio of the exposed surface of the active material particles on the surface opposite to the surface of the particle layer in contact with the resin substrate is 1 to 70 area%, which indicates that the resin substrate has a surface with a large surface area of ​​active material particles with excellent electronic conductivity and a surface with a large surface area of ​​solid electrolyte particles with excellent ion conductivity. By controlling the arrangement of the active material particles and solid electrolyte particles on the resin substrate, the area ratio of the exposed surface of the active material particles can be controlled. Specifically, the area ratio of the exposed surface of the active material particles can be controlled by arranging the active material particles and solid electrolyte particles by the method described later. Furthermore, by manufacturing an electrode using an electrode base material in which active material particles and solid electrolyte particles are arranged so as to have the above-mentioned configuration, it is possible to obtain an electrode having a configuration in which the active material particles have a large surface area on one surface and the solid electrolyte particles have a large surface area on the other surface. By manufacturing a secondary battery using an electrode having the above-described configuration, and arranging the surface of the active material particle having a larger surface area on the current collector side and the surface of the solid electrolyte particle having a larger surface area on the electrolyte layer side, electronic conduction and ion conduction can be smoothly performed, resulting in a secondary battery with reduced internal resistance of the electrode.

[0039] The difference between the area ratio of the exposed surface of the active material particles on the surface of the particle layer that contacts the resin substrate and the area ratio of the exposed surface of the active material particles on the surface of the particle layer opposite to the side that contacts the resin substrate is 1 to 70 area %, preferably 5 to 60 area %, more preferably 10 to 50 area %.

[0040] By making the difference 1% by area or more, electronic conduction and ion conduction can be smoothly achieved. Also, by making the difference 70% by area or less, it is possible to laminate the electrode base materials and to obtain an electric current. When forming the electrodes, the active material particles that contact each other in the stacking direction can be in sufficient contact with each other, and the efficiency of electronic conduction can be maintained high. By setting the difference between the areas to 1 to 70% by area, the ionic conductivity and electronic conductivity can be improved, and the internal resistance can be further suppressed.

[0041] The area ratio of the exposed surface of the active material particles to the surface of the particle layer is preferably 10 to 80% by area, more preferably 20 to 75% by area, and even more preferably 25 to 70% by area. In the particle layer, the surface with a larger area ratio of the surface of the active material particles exposed may be either the upper surface side or the lower surface side of the particle layer, i.e., the surface on the side in contact with the resin substrate, or the surface opposite to the side in contact with the resin substrate. It is preferable that the area ratio of the exposed surface of the active material particles on the surface of the particle layer that contacts the resin substrate is larger than the area ratio of the exposed surface of the active material particles on the surface opposite to the side contacting the resin substrate of the particle layer. In this case, the difference is a value obtained by subtracting the area ratio of the exposed surface of the active material particles on the surface opposite to the side contacting the resin substrate of the particle layer from the area ratio of the exposed surface of the active material particles on the surface of the particle layer that contacts the resin substrate.

[0042] For example, first particles P1 as active material particles and second particles P2 as solid electrolyte particles are arranged on a resin substrate as a material of the electrode substrate by a method described later, whereby the active material particles and the solid electrolyte particles can be controlled to be arranged adjacent to each other in the electrode substrate. Furthermore, when the particle layer is viewed through from the surface side in contact with the resin substrate or the surface side opposite to the surface in contact with the resin substrate, the solid electrolyte particles are arranged so as to cover a part of the surface of the active material particles. It can be confirmed, for example, by observation with an SEM that the particle layer is formed in the electrode substrate, that the active material particles and the solid electrolyte particles are arranged adjacent to each other, and that the solid electrolyte particles are arranged so as to cover the surfaces of the active material particles.

[0043] For example, when the electrode substrate is observed from the cross section, the resin substrate, the active material particles, and the solid electrolyte particles are arranged in this order from the lower side (the side on which the particle layer is not formed) of the electrode substrate. On the surface of the upper side (the side opposite to the resin substrate) of the electrode substrate, the solid electrolyte particles are arranged so as to cover at least a part of the surface of the active material particles. In addition, the solid electrolyte particles are arranged in the part of the resin substrate on which the active material particles are not arranged.

[0044] That is, in the particle layer in the electrode substrate, the solid electrolyte particles are densely arranged on the side in contact with the resin substrate or on the surface opposite to the resin substrate side, and a large number of active material particles are arranged on the surface opposite to the above surface. With such a configuration, electronic conduction can be smoothly achieved on the surface on which a large number of active material particles are arranged, and ionic conduction can be smoothly achieved on the surface on which the solid electrolyte particles are densely arranged.

[0045] In the present disclosure, the active material particles and solid electrolyte particles present on the resin substrate are identified in an SEM image of a cross section of the electrode substrate, and the area ratio of the exposed active material particles is compared between the resin substrate side and the opposite side to calculate the difference. The method of identifying the active material particles and the solid electrolyte particles and the method of calculating the area ratio will be described later.

[0046] A schematic diagram of an electrode substrate in the present disclosure is shown in FIG. 1. For the sake of explanation, particles P1 and P2 are described as spherical and with the same particle diameter. Particle P1 represents an active material particle, and particle P2 represents a solid electrolyte particle. Solid electrolyte particle P2 is disposed in a portion of the resin substrate where active material particle P1 is not disposed. Solid electrolyte particle P2 is disposed so as to cover a portion of the surface of active material particle P1 on the surface of the particle layer opposite to the resin substrate side. In FIG. 1, the surface of the active material particle is exposed over a large area on the surface of the particle layer facing the resin substrate, and the resin substrate is not exposed. The surface area of ​​the active material particles exposed on the surface opposite the oil base material side is small.

[0047] Active material particles often have higher electronic conductivity than solid electrolyte particles, and the degree of contact between active material particles tends to affect electronic conductivity within the electrode. Therefore, when the electrode substrates are laminated by the method described below, the active material particles and the solid electrolyte particles, the active material particles among themselves, or the solid electrolyte particles among themselves in the lamination direction of the electrode substrates can be sufficiently contacted without being hindered. This allows the ion conductivity of the secondary battery to be kept high and the rate characteristics to be improved. In addition, since more active material particles can be arranged on the electrode substrate, a battery with a high volumetric energy density can be manufactured.

[0048] <Method of manufacturing electrode substrate> Hereinafter, an example of a method for producing an electrode substrate will be described in detail with reference to the drawings. Although a positive electrode substrate using positive electrode active material particles will be described as an example, the method for producing an electrode substrate can be used for both positive and negative electrodes.

[0049] The method for producing the electrode substrate includes the following steps. (1) A preparation step of preparing a resin substrate having an adhesive portion. (2) A first step (S101 in FIG. 2) of disposing first particles P1 on the surface of the adhesive portion. (3) A second step (S102 in FIG. 2) of rubbing the surfaces of the first particles P1 arranged on the surface of the adhesive portion. (4) A third step (S103 in FIG. 2) of disposing second particles P2 on the surface of the adhesive portion and the rubbed surfaces of the active material particles

[0050] (preparation process) In the preparation step, a resin substrate having an adhesive portion is prepared. In the present disclosure, the term "having an adhesive portion" refers to an adhesive portion being provided on a part or the entire surface of the resin substrate. The resin substrate may be a substrate containing the above-mentioned resin. The method for providing the adhesive portion is not particularly limited, but a method of applying an adhesive to the surface of the resin substrate is preferable. The adhesive is not particularly limited, and any known adhesive can be used, for example, an acrylic adhesive, a rubber adhesive, a silicone adhesive, or a thermoplastic resin or a photocurable resin whose adhesive strength changes depending on disturbances such as heat or light.

[0051] (Step 1, Step 2 and Step 3) The first step is to arrange active material particles on the surface of the adhesive part of the resin substrate. The second step is to rub the surface of the active material particles arranged on the surface of the adhesive part. The third step is to arrange second particles P2 on the surface of the adhesive part where the active material particles are not arranged and on the rubbed surface of the active material particles. In the present disclosure, "rubbing" refers to contacting the surface of the active material particle with a magnetic particle or a member of a rubbing device described later, and rubbing the surface of the active material particle by moving the device while applying pressure. As described later, a rubbing step may be further performed after arranging the second particle P2, in which case the surfaces of the active material particle and the second particle P2 may be contacted with a magnetic particle or the above member, and the surfaces of the active material particle and the second particle P2 may be rubbed by moving the device while applying pressure. The rubbing is preferably performed using a magnetic particle. That is, the rubbing step preferably includes a step of rubbing the surface of the active material particle with a magnetic particle.

[0052] The first particles P1 are active material particles. For example, the above-mentioned active material particles can be used as the first particles P1. The particle size of the primary particles of the first particles P1 is not particularly limited. For example, the particle size distribution based on volume is The cumulative 10% particle size (r10) in the volumetric particle size distribution is preferably 0.1 to 10.0 μm, and more preferably 1.0 to 7.0 μm. The cumulative 50% particle size (r50) in the volumetric particle size distribution is preferably 0.5 to 20.0 μm, and more preferably 2.0 to 10.0 μm. Furthermore, the cumulative 90% particle size (r90) in the volumetric particle size distribution is preferably 2.0 to 20.0 μm, and more preferably 3.0 to 15.0 μm.

[0053] The second particles P2 are solid electrolyte particles. For example, the above-mentioned solid electrolyte particles can be used as the second particles P2. The particle size of the primary particles of the second particles P2 is not particularly limited. For example, the cumulative 10% particle size (r10) in the volume-based particle size distribution of the primary particles of the second particles P2 is preferably 0.5 to 10.0 μm, more preferably 1.0 to 7.0 μm. Furthermore, the cumulative 50% particle size (r50) in the volume-based particle size distribution is preferably 1.0 to 20.0 μm, more preferably 5.0 to 15.0 μm. Furthermore, the cumulative 90% particle size (r90) in the volume-based particle size distribution is preferably 5.0 to 50.0 μm, more preferably 10.0 to 30.0 μm.

[0054] The ratio of the particle size of the primary particles of the first particles P1 to the particle size of the primary particles of the second particles P2 is not particularly limited. For example, the ratio {(r50(P1)) / (r50(P2))} of the cumulative 50% particle diameter (r50(P1)) in the volume-based particle size distribution of the primary particles of the first particle P1 to the cumulative 50% particle diameter (r50(P2)) in the volume-based particle size distribution of the primary particles of the second particle P2 is preferably 0.05 to 20.0, and more preferably 0.1 to 2.0.

[0055] As described above, the first particles P1 are active material particles. The second particles P2 are solid electrolyte particles. That is, in the manufacturing method of the electrode substrate, the first and third steps can be said to be steps of arranging the active material particles and the solid electrolyte particles on the surface of the adhesive part. By inserting the second step between the first and third steps, a denser and more uniform particle layer can be formed.

[0056] In addition, an additional step may be provided between each step or after step 3. Examples include a step of arranging the third particles P3, a step of rubbing the arranged third particles P3, etc. The third particles P3 include graphite particles, active material particles, and solid electrolyte particles. In the first and third steps, particles are arranged on the adhesive portion of the resin substrate using a particle arrangement device. Hereinafter, particle arrangement device 1 and particle arrangement device 2 that can be used will be described in order.

[0057] [Particle placement device 1] FIG. 3 is a diagram showing a schematic configuration of the particle arrangement device 1. As shown in FIG. The particle placement device 1 has a first storage container 21a that stores and supplies a first substrate 11a, a first belt device 22a that transports the first substrate 11a, and a pattern forming device 23 that forms a concave-convex pattern on the first substrate 11a.

[0058] The particle arrangement device 1 has a first filling device 24a that arranges first particles P1 in the recesses of the concave-convex pattern formed on the first base material 11a. The particle arrangement device 1 has a second storage container 21b that stores and supplies the second base material 11b, and a second belt device 22b that transports the second base material 11b. ... The rollers 223 of the first substrate 11a and the second substrate 11b face each other at a transfer section 25a, and the first particles P1 are transferred from the first substrate 11a to the second substrate 11b at the transfer section 25a.

[0059] The particle arrangement device 1 has a rubbing device 30 that rubs the surfaces of the first particles P1 transferred onto the first base material 11b. Furthermore, the particle arrangement device 1 has a second filling device 24b that arranges second particles P2 in a non-transfer portion on the second base material 11b. Note that illustrations and detailed descriptions of devices that are less relevant to explaining the effects of the present invention, such as a peeling and collecting device for peeling and collecting the first base material 11a after transfer from the first belt device 22a and each cleaning device, are omitted.

[0060] In the particle arrangement device 1, the pattern forming device 23, the first filling device 24a, and the transfer unit 25a correspond to a first arrangement means that arranges the first particles P1 in a pattern on the second base material 11b. The rubbing device 30 corresponds to a means for rubbing the first particles. The second filling device 24b corresponds to a second arrangement means that arranges the second particles P2 in areas on the second base material 11b where the first particles P1 are not arranged. Hereinafter, a method for arranging particles on substrate 11 using particle arrangement device 1 will be described following the flow of each process.

[0061] First, the first substrate 11a is supplied from the first storage container 21a to the first belt device 22a by a supplying means (not shown). When the ultraviolet-curable liquid is applied by a pattern forming device 23 (described later), it is preferable that at least the surface of the first base material 11a is made of a material that has high wettability with the ultraviolet-curable liquid. In addition, it is preferable that the surface of the first base material 11a is smooth. The first substrate 11a may be a sheet made of a resin such as polyester that has been subjected to a hydrophilic or lipophilic treatment according to the ultraviolet-curable liquid (water-based or oil-based) to be used. The first substrate 11a may be a substrate that is individually cut like cut paper, a continuous substrate wound in a roll like roll paper, or a continuous substrate that is alternately folded like continuous paper.

[0062] The first belt device 22a transports the supplied first base material 11a to a pattern forming position of the pattern forming device 23. The first belt device 22a has driving rollers 221a and 222a, a pressure roller 223a, and a belt-like transport member 224a suspended between them. At this time, the pressure roller 223a is rotated by being driven.

[0063] The conveying member 224a is preferably made of resin or metal, and may be, for example, a polyimide resin belt. The driving rollers 221a and 222a are preferably made of metal, and may be, for example, stainless steel metal rollers. The pressure roller 223a is preferably a soft roller having an elastic layer on its surface, and may be, for example, a soft roller having a silicone rubber elastic layer on the surface of a stainless steel core. 3, the first belt device 22a is used as a conveying device for conveying the first base material 11a, but a roller device may be used instead of the belt device. The same applies to the second belt device 22b described later.

[0064] The pattern forming device 23 forms a fine concave-convex pattern on the first base material 11a transported to the pattern forming position. Methods for forming the concave-convex pattern include a UV imprint method, a thermal imprint method, a UV inkjet method, a printing method, and a laser etching method.

[0065] When the pattern forming device 23 forms a concave-convex pattern by the UV imprint method, the pattern forming device 23 has a coating means for coating an ultraviolet-curable liquid on the first base material 11a. As the ultraviolet-curable liquid, for example, an ultraviolet-curable resin such as an ultraviolet-curable liquid silicone rubber can be used. The pattern forming device 23 also has an imprinting means for imprinting a mold having a concave-convex pattern formed on its surface onto the ultraviolet-curable liquid on the first base material 11a, and a light source for irradiating the ultraviolet-curable liquid with ultraviolet rays. Typically, an ultraviolet-curable liquid silicone rubber (PDMS) or resin is used as the ultraviolet-curable liquid, a film mold is used as the mold, and a UV lamp is used as the light source.

[0066] When the first filling device 24a fills the recesses on the substrate 11a with the first particles P1 using the support material S1 carrying the first particles P1, the opening diameter (width) of the recesses in the concave-convex pattern on the first substrate 11a is preferably larger than the cumulative 50% particle diameter (median diameter) based on volume of the first particles P1. Also, the opening diameter (width) of the recesses is preferably smaller than the average size of the support material S1. Here, the opening diameter of the recesses in the concave-convex pattern is preferably the opening diameter in the short side direction of the recesses, and more preferably the maximum opening diameter in the short side direction of the recesses.

[0067] The width of the recess can be appropriately adjusted depending on the particle sizes of the first particles P1 and the support material S1, etc. The width of the recess is not particularly limited, but is preferably, for example, 0.2 to 30 μm, and more preferably 2 to 15 μm.

[0068] By setting the opening diameter of the recesses of the uneven pattern as described above, the first particles P1 can contact the bottom and side (typically the bottom) of the recesses of the uneven pattern. On the other hand, the support material S1 cannot contact the bottom and side of the recesses. This allows the first particles P1 that contact the bottom and side of the recesses to be captured by the uneven pattern, while the support material S1 can be prevented from being captured by the uneven pattern. In other words, it is preferable that the first particles P1 can contact the bottom and side of the recesses of the uneven pattern, and the first support material S1 cannot contact the bottom and side of the recesses of the uneven pattern.

[0069] Although the pattern forming device 23 forms an uneven pattern on the first substrate 11a, a substrate on which an uneven pattern has been formed in advance on its surface may be used as the first substrate 11a. Alternatively, the pattern forming device 23 may directly form an uneven pattern on the surface of the transport member 224a of the first belt device 22a, or a transport member having an uneven pattern on its surface may be used as the transport member 224a. In this case, in consideration of durability, it is preferable to use a metal belt such as stainless steel or aluminum, and form an uneven pattern on the surface by a micromachining technique such as laser etching, wet etching, or dry etching. The first base material 11a having the concave-convex pattern formed on its surface is transported by the first belt device 22a to the filling position of the first filling device 24a.

[0070] 4 is a diagram showing a schematic configuration of the filling device. The configuration of the first filling device 24a will be described below, but the same applies to the second filling device 24b. The first filling device 24a has a filling container 242a that contains a filler 241a, a stirring screw member 243a that stirs and conveys the filler 241a, a recovery member 244a that recovers the filler, and a magnetic member 247a.

[0071] The filler 241a has first particles P1 and a support material S1 that supports the first particles P1. The filler 241a is a mixture of multiple powders including a powder composed of multiple first particles P1 and a powder composed of multiple support materials S1. The filler 241a contained in the filling container 242a is sufficiently mixed when it is stirred and transported by the stirring screw member 243a. As a result, the first particles P1 are supported on the surface of the support material S1. The forces acting between particles when they are supported include electrostatic forces due to frictional charging, van der Waals forces, liquid bridging forces, and the like.

[0072] The support material S1 is a magnetic particle. The support material S1 is preferably a particle in which the surface of a resin particle in which ferrite core particles or a magnetic body is dispersed is coated with a resin composition. For example, a standard carrier (Standard Carrier P02 manufactured by the Imaging Society of Japan), which is a magnetic particle, can be used. The particle size and material of the support material S1 are appropriately selected according to the particle size and material of the first particles P1. This allows the support material S1 to stably support the first particles P1. In addition, even if the first particles P1 have a small particle size and tend to aggregate, the support material S1 plays a role of loosening the particles by stirring and transporting them. The particle size of the support material S1 can be appropriately adjusted by changing the size (area, width, depth) of the recesses. For example, the volume-based cumulative 50% particle size (median size) is preferably 50 to 100 μm.

[0073] Recovery member 244a has roller 245a rotatable in the direction of arrow d2 in the figure, and magnet 246a arranged inside roller 245a and fixed to filling container 242a. Magnetic member 247a is arranged facing filling container 242a via transport member 224a, and has magnet 248a inside.

[0074] The magnet 246a has a plurality of N poles and S poles arranged alternately along the rotation direction of the recovery member 244a. The magnet 248a has a plurality of N poles and S poles arranged alternately along the transport direction of the transport member 224a. The magnet 246a has a magnetic pole (N1 pole in FIG. 4) of a different polarity at a position closest to and facing the most downstream magnetic pole (S1 pole in FIG. 4) of the magnet 248a, and an N2 pole of the same polarity as the N1 pole is arranged at the most downstream position.

[0075] The magnet 246a and the magnet 248a may be composed of a plurality of magnets, and the type of magnets constituting the magnet 246a and the magnet 248a is not particularly limited. For example, a permanent magnet such as a rare earth magnet, a ferrite magnet, a neodymium magnet, a samarium-cobalt magnet, or a plastic magnet, or a means for generating a magnetic field such as an electromagnet can be used. The magnet 248a may be configured to be movable in the transport direction of the first base material 11a or in the opposite direction.

[0076] In addition, a regulating member for regulating the filler 241a on the first base material 11a or a collecting member for re-collecting the filler 241a that cannot be collected by the collecting member 244a may be provided upstream or downstream of the collecting member 244a in the transport direction of the transport member 224a. As the collecting member for re-collecting, in addition to a member similar to the collecting member 244a, a simple member such as a fixed magnet or a regulating member, or a collecting member that collects by air blowing can be used.

[0077] Next, the process of filling the recesses on the first base material 11a with the first particles P1 by the first filling device 24a will be described with reference to FIGS. As the first conveying member 224a moves in the direction of the solid arrow d1 in FIG. 4, the first base material 11a carried and conveyed by the first conveying member 224a is conveyed to the filling position of the first filling device 24a.

[0078] The filler 241a is transported by the stirring screw member 243a and supplied onto the first substrate 11a (dotted line a in FIG. 4). At this time, a magnetic field is formed by the magnetic member 247a and the recovery member 244a, and the filler 241a containing the support material S1, which is a magnetic particle, forms a plurality of magnetic chains on the first substrate 11a due to the magnetic field. The filler 241a supplied onto the first substrate 11a is transported on the first substrate 11a while forming magnetic chains as the first substrate 11a moves (dotted line b in FIG. 4).

[0079] 5A, 5B, and 5C are schematic diagrams of the filler 241a being transported on the first substrate 11a. For the sake of explanation, the filler 241a other than the filler forming one magnetic hair is omitted from the illustration. As described above, the filler 241a on the first substrate 11a forms a magnetic hair along the magnetic field lines of the formed magnetic field, and is transported while changing the shape of the magnetic hair as shown in FIG. 5A, FIG. 5B, and FIG. 5C with the movement of the first substrate 11a. At this time, since a particularly strong magnetic force acts in the vicinity of the magnet 248a, the transport speed v2 of the filler 241a is smaller than the moving speed v1 of the first substrate 11a when the filler 241a moves away from the magnetic pole, and is larger in the opposite case. That is, the filler 241a on the first substrate 11a has a relative speed that is not 0 with respect to the first substrate 11a.

[0080] Fig. 6 is an enlarged view of the vicinity of the surface of the first base material 11a in Fig. 5A to C. Although not shown in Fig. 5A to C, an uneven pattern 111a is formed on the first base material 11a as shown in Fig. 6. The uneven pattern can be formed as a desired pattern such as a honeycomb pattern or a line pattern.

[0081] The filler 241a comes into contact with the concave-convex pattern 111a, and is transported together with the first substrate 11a while being subjected to a magnetic force (solid line Fm in the figure) in a direction perpendicular to the surface of the first substrate 11a and having a non-zero relative speed with respect to the first substrate 11a. As a result, the first particles P1 supported on the support material S1 are transported while being rubbed against the concave-convex pattern 111a on the surface of the first substrate 11a.

[0082] At this time, the particle size of the first particles P1 is smaller than the opening diameter of the recesses of the uneven pattern 111a, and the particle size of the first support material S1 is larger than the opening diameter of the recesses, so the first particles P1 can contact the bottom surface (bottom part) and side parts of the recesses of the uneven pattern 111a, but the support material S1 cannot. That is, only the first particles P1 in the filler 241a selectively contact the bottom surface and side parts of the recesses.

[0083] The first particles P1 that come into contact with the recesses are strongly bound by a physical binding force due to the structure of the concave-convex pattern 111a and non-electrostatic adhesive forces such as electrostatic adhesion and adhesive forces with the structural materials that constitute the first base material 11a and the concave-convex pattern 111a, and are detached from the support material S1. Note that, for the sake of explanation, in Fig. 6, the first particles P1 are supported on the surface of the support material S1, but it is acceptable for the first particles P1 to be present that are not supported by the support material S1 during the mixing, supply, or transport of the filler 241a.

[0084] Downstream of the magnetic member 247a, the recovery member 244a is disposed with a gap between it and the first transport member 224a, as shown in Fig. 4. As the first base material 11a moves, the filler 241a transported to the vicinity of the most downstream magnetic pole (pole S1) of the magnet 248a moves from the first base material 11a to the recovery member 244a under the influence of the magnetic field formed by the magnet 246a, and is recovered (dotted line c in Fig. 4).

[0085] As described above, in the transport process (dotted lines a, b, and c in FIG. 4), the recesses of the concave-convex pattern 111a on the surface of the first base material 11a are in sufficient contact with the plurality of fillers 241a. Therefore, the first particles P1 are selectively and densely arranged in the recesses of the concave-convex pattern 111a after the fillers 241a are collected by the collection member 244a.

[0086] In addition, in Figs. 5A to 5C and 6, the first particles P1 are all shown with the same particle size, but in reality there is a particle size distribution, and furthermore, depending on the material, the particles may aggregate to form secondary particles. In addition, the particles may not have a spherical shape as shown. Even in such cases, only the particles that can contact the recesses of the uneven pattern 111a are selectively densely packed, so that the arrangement of the particles Coarse powder and secondary particles that may adversely affect the process are easily removed.

[0087] In this way, the amount of the first particles P1 filled into the recesses of the concave-convex pattern 111a can be controlled by the size (area, width, height) of the concave-convex pattern and the particle size of the first particles P1. Specifically, the area of ​​the recesses is approximately the filled area, and the layer thickness of the filled first particles P1 is determined by the height of the protrusions.

[0088] The pitch of the convex portions is not particularly limited, but is preferably, for example, 1.0 to 20 μm, and more preferably 2.0 to 15 μm. The height of the convex portions is not particularly limited, but is preferably, for example, 0.1 to 20.0 μm, and more preferably 1.0 to 10.0 μm. The area ratio of the recesses (the ratio of the recesses to the area of ​​the recessed and concave pattern) is not particularly limited, but is preferably, for example, 50% or more, and more preferably 70% or more.

[0089] For example, to obtain a thin layer (single layer) that is 50% of the substrate area, the area ratio of the recesses (area ratio of the recesses to the entire recessed / protruding pattern) should be controlled to 50%, and the depth of the recesses should be controlled to the particle size of the first particles P1 or less. In this case, the opening width of the recesses should be larger than the median diameter of the first particles P1 and smaller than the average size (here, the average particle size) of the support material S1.

[0090] The first particles P1 may have a wide particle size distribution, but the support material S1 preferably has a narrow particle size distribution, and more preferably is monodisperse. This makes it easier to prevent the support material S1 from contacting the bottom (or bottom surface) or side of the recess. If the support material S1 can contact the bottom or side of the recess, there is a risk that the support material S1 will be restrained and filled in the recess.

[0091] Furthermore, the opening width of the recesses of the uneven pattern 111a is preferably smaller than four times the particle diameter of the first particles P1. By making the opening width smaller than four times the particle diameter of the first particles P1, the probability that the first particles P1 will come into contact with two points, the bottom and side surfaces of the recesses of the uneven pattern 111a, can be increased. In this way, the first particles P1 that come into contact with the recesses of the uneven pattern 111a at multiple points are strongly constrained by the uneven pattern 111a, and therefore the efficiency of filling the uneven pattern 111a with the first particles P1 can be increased. The same applies to the particle size of the second particles P2 described later and the size of the recesses of the uneven pattern formed by the first particles P1 on the second base material. In addition, when brush fibers are used as the support material, the "average particle size of the support material" in the above explanation becomes the "average fiber diameter of the support material."

[0092] The filler 241a collected by the collecting member 244a is transported by the roller 244a which is a rotating collecting member (dotted line in FIG. 4, d). The filler 241a transported by the roller 244a falls into the filling container 242a (dotted line in FIG. 4, e) due to the magnetic field of two adjacent and repelling same-polarity magnetic poles (N1, N2) and the influence of gravity. Thereafter, the filler 241a is stirred and transported again by the stirring screw member 243a, and this process is repeated thereafter.

[0093] The mass ratio of the first particles P1 and the support material S1 in the filler 241a in the filling container 242a is determined by an inductance sensor that measures using magnetic permeability, a patch concentration sensor that measures and predicts the reflection density on a substrate, etc., which are common in electrophotographic devices. At least one of the first particles P1 and the support material S1 is replenished by a replenishing means (not shown) as necessary. This allows stable filling over a long period of time.

[0094] The mass % of the first particles P1 in the filler 241a (the ratio of the mass of the first particles P1 to the total mass of the filler 241a) is calculated based on the surface area of ​​the magnetic particles (support material) to be supported. Using the coverage S1 of the first particles P1, it is expressed by the following formula (1): The coverage S1 indicates the ratio of the total cross-sectional area of ​​the first particles P1 to the surface area of ​​the magnetic particles (support). Mass% of the first particles P1 in the filler 241a=(400×ρ P1 ×r P1 ×S1) / ( 100×ρ c ×r c +4×ρ P1 ×r P1 ×S1) Formula (1) (The descriptions in formula (1) are as follows: ρ P1 : true density of the first particle P1, r P1 : particle size of the first particle P1 (r50), ρ c : true density of magnetic particles, r c : particle size of the magnetic particle (r50), S1: coverage rate of the first particle P1 to the surface area of ​​the magnetic particle)

[0095] The mass % of the first particles P1 in the filler 241a is not particularly limited, but is preferably in the range of 5 to 40 mass %, or 10 to 30 mass %. Moreover, the coverage S1 in the above formula (1) is preferably adjusted to be 30 to 200 area %, and more preferably adjusted to be 50 to 100 area %. The particle diameter (r50) of the first particle P1 and the magnetic particle (support material) can be determined by laser diffraction scattering type particle size distribution measurement, and the true density of the first particle P1 and the magnetic particle (support material) can be determined by the pycnometer method.

[0096] Although the filling device described here uses magnetic particles as a carrier material to form a so-called magnetic brush and fills the recesses with the particulate material, the type of filling device is not limited to this. Brush fibers can also be used as the carrier material. Alternatively, an elastic material, at least the surface of which is made of an elastic body, can also be used as the carrier material.

[0097] FIG. 7A is a diagram showing a schematic configuration of a filling device 24c in the case where brush fibers are used as the support material. The filling device 24c has a roller 2410 having brush fibers on its surface. The roller 2410 is a so-called brush roller, with brush fibers planted on its surface. The material of the fibers constituting the brush fibers of the roller 2410 may be, for example, nylon, rayon, acrylic, vinylon, polyester, or vinyl chloride. The surface of the fibers may be subjected to a surface treatment in order to adjust the electrostatic charge property or rigidity.

[0098] The filling device 24c has a supplying member that supplies the filler 241a to the roller 2410. The filler 241a contains a powder including the first particles P1, and is contained in a filling container 242a. In this example, the filler 241a does not contain the carrier material S1, which is a magnetic particle. The filler 241a is stirred and transported by a stirring screw member 243a, and is supplied to a supplying member 249.

[0099] The supply member 249 is a member that supplies the filler 241a to the roller 2410, and its configuration is not particularly limited. For example, the supply member 249 can be a roller having at least a surface made of a porous foam material having elasticity. Typically, an elastic sponge roller having a foamed skeletal structure and having a relatively low hardness polyurethane foam formed on a core metal can be used. Note that, in addition to urethane, various rubber materials such as nitrile rubber, silicone rubber, acrylic rubber, hydrin rubber, and ethylene propylene rubber can be used as the material of the foam material.

[0100] The supplied filler 241a is filled into the foam material on the surface of the supply member 249, and is transported to a supply section that comes into contact with the roller 2410. In the supply section, the filler 241a filled into the foam material is charged by contact with the brush fibers of the roller 2410, and is carried by the brush fibers of the roller 2410. Furthermore, the supply member 249 may also have a function of peeling off the filler 241a remaining on the roller 2410 and refreshing it. The filler 241a supplied to the roller 2410 comes into contact with the first base material 11a by the movement of the brush fibers.

[0101] At this time, the first particles P1 in the filler 241a can contact the bottom and side surfaces of the recesses of the uneven pattern 111a on the surface of the first base material 11a, but the brush fibers cannot. That is, the fiber diameter of the brush fibers is made larger than the opening width of the recesses of the uneven pattern 111a. The fiber diameter of the brush fibers can be measured by placing glass on the surface of the roller 2410 and taking an image of the brush fibers through the glass using an optical microscope. At this time, the fiber diameters of about 100 brush fibers are measured, and the distribution of the fiber diameters is measured to calculate the average diameter.

[0102] The movement of the transport member 224a and the rotation of the roller 2410 cause the brush fibers of the roller 2410 to rub against the surface of the first base material 11a. As a result, the first particles carried by the brush fibers are densely arranged in the recesses of the uneven pattern 111a on the surface of the first base material 11a.

[0103] FIG. 7B is a diagram showing a schematic configuration of a filling device 24d when an elastic material is used as the support material. The filling device 24d has a similar configuration to the filling device 24c, but differs in that a roller 2411 having an elastic material is used instead of the roller 2410 having brush fibers. The roller 2411 is a roller having an elastic layer formed on its surface.

[0104] The elastic layer is formed of a material having elasticity, such as a rubber material, such as silicone rubber, acrylic rubber, nitrile rubber, urethane rubber, fluororubber, etc. The surface shape of the elastic layer may be controlled by adding fine particles, such as spherical resin particles. When the elastic layer has a convex portion on its surface, the size of the convex portion of the elastic layer is set to be larger than the size of the concave portion of the concave-convex pattern 111a. The size of the convex portion of the elastic layer can be measured in the same manner as the fiber diameter of the brush fiber described above.

[0105] The movement of the transport member 224a and the rotation of the roller 2411 causes the elastic material on the surface of the roller 2411 to rub against the surface of the first base material 11a. As a result, the first particles supported by the elastic material are densely arranged in the recesses of the concave-convex pattern 111a on the surface of the first base material 11a.

[0106] By using brush fibers or elastic materials as the carrier material as in Figures 7A and 7B, it is not necessary to include magnetic particles in the filler. In addition, the configuration of the filling device can be simplified. On the other hand, when magnetic particles are used as the carrier material as in Figure 4, there is a higher degree of freedom in the size and shape of the carrier material than in the case of brush fibers or elastic materials. In addition, the carrier material can move more freely on the substrate when magnetic particles are used.

[0107] For these reasons, when magnetic particles are used as the support material, the particles such as the first particles P1 can be more efficiently supplied onto the substrate, and the recesses on the substrate can be more efficiently filled. Also, when a magnetic material is used as the support material, even if the support material deteriorates during the process, the support material can be replenished or replaced without stopping the process.

[0108] The method of filling the recesses with particles by rubbing the support material carrying the particles allows a larger amount of dispersed particles to be supplied to the recesses, and allows for stable and dense filling, compared to a filling method using a restricting member such as a blade. This advantage is more pronounced as the particle size of the particles to be filled becomes smaller, since the particles tend to aggregate.

[0109] The first base material 11a, in which the concaves of the concave-convex pattern 111a have been filled with the first particles P1 by the first filling device 24a, is transported to the transfer section 25a by the first belt device 22a. Here, the second belt device 22b has the same structure as the first belt device 22a as shown in FIG. The transfer section 25a includes driving rollers 221b and 222b, a pressure roller 223b, and a belt-like conveying member 224b suspended between the driving rollers 221b and 222b. At this time, the pressure roller 223b is driven to rotate. In the transfer section 25a, the pressure roller 223a of the first belt device 22a and the pressure roller 223b of the second belt device 22b face each other.

[0110] The second substrate 11b is supplied from the second storage container 21b to the second belt device 22b and transported in the direction of the arrow in Fig. 4. The supplied second substrate 11b is transported in accordance with the timing at which the first substrate 11a is transported to the transfer section 25a. In the transfer section 25a, the first particles P1 filled in the first substrate 11a are transferred to the second substrate 11b.

[0111] That is, the first substrate 11a can be called a transfer substrate for transferring the first particles P1 to the second substrate 11b. The concave-convex pattern formed on the surface of the first substrate 11a can be called a transfer concave-convex pattern. Hereinafter, this transfer process will be described with reference to FIG. 8.

[0112] 8 is a diagram showing a schematic configuration of the transfer unit 25a. The transfer unit 25a is composed of the pressure roller 223a and the conveying member 224a of the first belt device 22a, and the pressure roller 223b and the conveying member 224b of the second belt device 22b. As described above, the pressure rollers 223a and 223b rotate drivenly, and the two rollers are in contact with each other via the conveying members 224a and 224b. At least one of the pressure rollers 223a and 223b is a soft roller having an elastic layer on its surface, and a nip portion is formed at the portion where the two rollers are in contact with each other.

[0113] The first substrate 11a and the second substrate 11b filled with the first particles P1 by the first filling device 24a are transported at substantially equal speeds by the respective transport members (224a and 224b) and enter a nip portion formed by contact between the pressure rollers 223a and 223b. In the nip portion, the first particles P1 on the first substrate 11a come into contact with the second substrate 11b and are transferred onto the second substrate 11b.

[0114] The second substrate 11b is a substrate having a stronger adhesive force to the first particles P1 than the adhesive force of the first substrate 11a to the first particles P1. In other words, the adhesive force of the first particles P1 to the second substrate 11b is stronger than the adhesive force of the first particles P1 to the first substrate 11a. As a result, the first particles P1 on the first substrate 11a are transferred onto the second substrate 11b at the nip portion.

[0115] The material of the second substrate 11b is not particularly limited, and a substrate made of the same material as the first substrate 11a can be used. Note that, like the first substrate 11a, the second substrate 11b may be a substrate that is individually cut off like cut paper, a continuous substrate that is wound into a roll like roll paper, or a continuous substrate that is alternately folded like continuous paper.

[0116] The second substrate 11b is preferably subjected to a surface treatment for increasing adhesion in order to transfer the contacted first particles P1. For example, the second substrate 11b preferably has an adhesive portion on its surface where an adhesive is applied. As a preparation step for preparing a resin substrate having an adhesive portion, for example, the second substrate 11b is prepared. The thickness of the second substrate is not particularly limited, but is preferably, for example, 1 to 10 μm. The thickness of the adhesive portion is not particularly limited, but is preferably, for example, 0.1 μm or more, and more preferably, 0.5 μm or more.

[0117] Furthermore, the back surface of the second base material 11b (the surface to which the first particles P1 are not transferred) also has an adhesive portion coated with the same adhesive as the front surface, and the front surface is further covered with a protective film or the like. This can prevent the base materials from shifting when stacking as described below, and the active material particles and solid electrolyte particles between the base materials are sandwiched between the top and bottom surfaces (stacking direction) and strongly fixed, which results in suppressing particle movement during stacking of the electrode base materials, storage of the stack, heat treatment, and pressure application, and allows the desired electrode to be formed.

[0118] The adhesive is not particularly limited, and the above-mentioned adhesives can be used. The particle arrangement device 1 may also have an application means such as a dispenser, an inkjet head, a spin coater, or a bar coater that applies an adhesive to the surface of the second base material 11b during transportation. The type and amount of adhesive applied are appropriately adjusted depending on the shape and material of the concave-convex pattern used, and the particle size and material of the first particles P1 and the second particles P2, but it is preferable that the adhesive has a stronger adhesive strength than the concave-convex pattern 111a. Comparison of adhesive strengths can be measured by a general method using a nanoindenter.

[0119] In the nip portion, the first particles P1 are restrained by an adhesive force generated between the first particles P1 and the second substrate 11b. When the conveying members 224a and 224b pass the nip portion and are separated from each other, the first particles P1 on the first substrate 11a are transferred to the second substrate 11b.

[0120] The first particles P1 are disposed on the second substrate 11b that has passed through the transfer section 25a, but the adhesive portion is exposed in the portion where the first particles P1 are not disposed. In the second step, the first particles P1 arranged on the resin substrate are rubbed with magnetic particles having a particle size larger than the width of the exposed portion of the adhesive portion on the resin substrate. The second substrate 11b onto which the first particles P1 have been transferred is transported by the transport member 224b to the rubbing device 30. The rubbing device 24 has the same configuration and function as the first filling device 24a, except that a filler having a carrier material S3 is contained in the filling container 242a instead of the filler 241a having the first particles P1 and the carrier material S1.

[0121] The rubbing device 30 rubs the first particles P1 arranged on the resin base material using a carrier S3, which is magnetic particles with no particles attached, in the same manner as when the first particles P1 were filled. In the above-mentioned filling device, a magnetic material is used as a filler, and the magnetic material is brought into contact with the surface of the resin base material on which the first particles P1 are arranged, thereby rubbing the surface of the first particles P1. The support material S3 is not particularly limited as long as it is a magnetic particle, but it is preferable to use the same as the support material S1 described above. For example, a standard carrier (Standard Carrier P02 manufactured by the Japan Imaging Society) which is a magnetic particle can be used. The particle size and material of the support material S3 are appropriately selected according to the particle size and material of the first particles P1. The particle diameter of the support material S3 is preferably larger than the width of the portion on the resin substrate where the active material particles are not arranged. For example, the volume-based cumulative 50% particle diameter (median diameter) is preferably 50 to 100 μm. This allows the support material S3 to have a particle diameter that does not contact the adhesive portion exposed on the resin substrate, so that it can rub only the first particles P1 arranged on the substrate.

[0122] By rubbing the surface of the first particles P1 transferred onto the substrate 11b, the first particles P1 can be more firmly fixed to the adhesive portion on the substrate 11b, and particle loss or shifting in the subsequent process can be prevented. In addition, the packing density of the transferred first particles P1 increases, and even after the subsequently applied second particles P2 are applied, the electrode substrate is one in which the particles are packed very densely. Furthermore, by rubbing the first particles P1, the second particles P2 can easily ride on the surface of the first particles P1. In other words, the surface of the first particles P1 becomes a gently convex shape by rubbing, and the area that can come into contact with the second particles P2 can be increased. In addition, the second particles P2, which are arranged in the process described below, are arranged to a height approximately equal to the uppermost surface of the first particles P1. Therefore, by rubbing the first particles P1, the second particles P2 can be easily disposed on the first particles P1.

[0123] This makes it easier to configure the particle layer such that the second particles P2 cover at least a part of the surface of the first particles P1 on one surface, increasing the area ratio of the second particles P2. That is, it makes it easier to configure the particle layer such that there is a difference between the area ratio of the exposed surface of the active material particles on one surface and the area ratio of the exposed surface of the active material particles on the other surface.

[0124] The rubbed second base material 11b is transported by the transport member 224b to the loading position of the second loading device 24b. The second filling device 24b has the same configuration and function as the first filling device 24a, except that a filling material 241b having second particles P2 and a support material S2 is contained in a filling container 242a instead of a filling material 241a having first particles P1 and a support material S1.

[0125] The second filling device 24b fills the second particles P2 into the portion on the second substrate 11b where the first particles P1 are not arranged. As described above, the first particles P1 are arranged on the second substrate 11b that has passed through the transfer unit 25a, but the adhesive portion is exposed in the portion where the first particles P1 are not arranged, and a recess is formed, so to speak. The second filling device 24b fills the recess (adhesive portion) with the second particles P2 in the same process as the first filling device 24a.

[0126] In this manner, the second particles P2 that can be filled are selectively filled into gaps on the second base material 11b where the first particles P1 are not arranged, thereby improving the coverage rate of the base material by the particles. The second particles P2 preferably have a median diameter equal to or smaller than the opening width of the gap between the first particles P1. Note that, although the case where magnetic particles are used as the carrier material will be described here, brush fibers or elastic material may be used as the carrier material, as in the first filling device 24a.

[0127] The filler 241b has second particles P2 and a support material S2 that supports the second particles P2. The filler 241b is a mixture of multiple powders including a powder composed of multiple second particles P2 and a powder composed of multiple support materials S2. The support material S2 may be the same as the support material S1 or may be different. It is appropriately selected according to the particle size and material of the second particles P2 and the opening width of the above-mentioned void portion.

[0128] FIG. 9 is an enlarged view of the vicinity of the surface of the second substrate 11b in the filling process by the second filling device 24b. On the second substrate 11b, an uneven pattern is formed having convex portions formed by arranging the first particles P1 and concave portions where the first particles P1 are not arranged. The adhesive portion 13b is exposed in the concave portion on the second substrate 11b where the first particles P1 are not arranged. In the filling process by the second filling device 24b, the second particles P2 are arranged on the adhesive portion 13b on the surface of the second substrate 11b. After the filling process by the second filling device 24b, the first particles P1 and the second particles P2 are arranged adjacent to each other on the surface of the adhesive portion of the second substrate 11b. That is, by arranging the second particles P2 on the portion on the second substrate 11b where the first particles P1 are not arranged, the first particles P1 and the second particles P2 can be arranged adjacent to each other. Furthermore, it is not necessary that the second particles P2 are disposed adjacent to all of the first particles P1, and the first particles P1 or the second particles P2 may be adjacent to each other.

[0129] The filler 241b comes into contact with the concave-convex pattern and receives a magnetic force (solid line Fm in the figure) in a direction perpendicular to the surface of the second base material 11b, and has a non-zero phase with respect to the second base material 11b. The second particles P2 supported on the support material S2 are transported together with the second substrate 11b while maintaining a relative speed with respect to the support material S2. As a result, the second particles P2 supported on the support material S2 are transported while being rubbed against the concave-convex pattern on the surface of the second substrate 11b. The mass % of the second particles P2 in the filler 241b (the ratio of the mass of the second particles P2 to the total mass of the filler 241b) is expressed by the following formula (2) using the coverage S2 of the surface area of ​​the magnetic particles (support material) by the supported second particles P2. The coverage S2 indicates the ratio of the total cross-sectional area of ​​the second particles P2 to the surface area of ​​the magnetic particles (support material). Mass% of the second particles P2 in the filler 241b=(400×ρ P2 ×r P2 ×S2) / (100×ρ c ×r c +4×ρ P2 ×r P2 ×S2) Formula (2) (The descriptions in formula (2) indicate the following: ρ P2 : true density of the second particle P2, r P2 : Particle size of the second particle P2 (r50), ρ c : true density of magnetic particles, r c : particle size of the magnetic particle (r50), S2: coverage rate of the second particle P2 to the surface area of ​​the magnetic particle)

[0130] The mass % of the second particles P2 in the filler 241b is not particularly limited, but is preferably in the range of 5 to 40 mass %, or 10 to 30 mass %. Moreover, the coverage S2 in the above formula (2) is preferably adjusted to be 30 to 200 area %, and more preferably adjusted to be 50 to 100 area %. The particle diameter (r50) of the second particle P2 and the magnetic particle (support material) can be determined by laser diffraction scattering type particle size distribution measurement. The true density of the second particle P2 and the magnetic particle (support material) can be determined by the pycnometer method.

[0131] At this time, the opening width of the recesses of the uneven pattern is set to a size that allows the second particles P2 to contact the recesses but not the support material S2. That is, the opening diameter of the recesses of the uneven pattern on the second base material 11b is preferably larger than the cumulative 50% particle size (median diameter) in the volume-based particle size distribution of the second particles P2. Also, the opening diameter of the recesses is preferably smaller than the average size of the support material S2. Here, the opening diameter of the recesses of the uneven pattern is preferably the opening diameter in the short side direction of the recesses, and more preferably the maximum opening diameter in the short side direction of the recesses. This allows only the second particles P2 in the filler 241b to selectively contact the recesses.

[0132] The second particles P2 that come into contact with the recesses are strongly bound by the physical binding force due to the structure of the concave-convex pattern, and by electrostatic adhesion and adhesive force with the second base material 11b and the structural material that constitutes the concave-convex pattern (here, the first particles P1), and are detached from the support material S2. Note that, for the sake of explanation, in Fig. 9, the second particles P2 are supported on the surface of the support material S2, but it is acceptable for the second particles P2 to be present that are not supported by the support material S2 during the mixing, supply, or transport of the filler 241b.

[0133] 10A is a schematic diagram of the second substrate 11b after the first particles P1 are transferred by the transfer unit 25a, and is a diagram of the second substrate 11b viewed from a direction perpendicular to the substrate surface. As shown in FIG. 10A, a honeycomb pattern is formed on the second substrate 11b, in which the arrangement regions in which the first particles P1 are arranged in a regular hexagonal shape are aligned.

[0134] The first particles P1 are densely arranged within this regular hexagonal region, and the first particles P1 are not arranged in other parts (white parts in FIG. 10A), and the adhesive part of the surface of the second base material 11b is exposed. The regular hexagonal region in which the first particles P1 are held is another way of saying the first pattern part. Also, the honeycomb pattern region in which the second particles P2 are held and which corresponds to the gaps in the first pattern part is another way of saying the second pattern part.

[0135] FIG. 10B is a schematic diagram of the second base material 11b after the second particles P2 have been filled by the second filling device 24b, and is a diagram of the second base material 11b as viewed from a direction perpendicular to the base material surface. As shown in FIG. 10B, the second particles P2 are densely arranged in the area where the first particles P1 are not arranged and the adhesive portion is exposed. Also, the first particles P1 and the second particles P2 are densely arranged in the boundary between the area where the first particles P1 are arranged and the area where the second particles P2 are arranged. Note that the particles can be filled in the small gaps between the first particles P1 in the same manner. In this case, it is possible to fill the gaps between the first particles P1 in the same manner as described above using a filler containing particles with a particle size equivalent to the gaps between the first particles P1, and a more dense thin film can be formed.

[0136] [Particle placement device 2] 11 is a diagram showing a schematic configuration of the particle arrangement device 2. The particle arrangement device 2 is a device for forming a particle layer 12 on a substrate 11, and includes a storage container 21 for storing and supplying the substrate 11, and a belt device 22 for transporting the substrate 11. The particle arrangement device 2 may also include a liquid application device 201 for applying a liquid for providing an adhesive portion on the substrate 11. In this case, in order to densely arrange the particles on the substrate 11, it is preferable to apply the liquid in a pattern on the substrate 11.

[0137] As the liquid applying device 201, a device that ejects liquid by an inkjet method or a device that applies liquid can be used, but a plate-based method such as a flexographic plate can also be used. Among them, it is preferable to use a device that ejects liquid by an inkjet method as the liquid applying device. As a device for discharging liquid by the inkjet method, devices using various discharging methods, such as a thermal type, a piezoelectric type, an electrostatic type, and a continuous type, can be used.

[0138] The liquid applied by the liquid applying device 201 may be water-based or oil-based as long as it contains a material to which the first particles P1 can be attached. The liquid is appropriately selected, for example, by selecting a material that does not react with the first particles P1. The liquid applying device 201 may also form the pattern L1 with a plurality of types of liquid. For example, the liquid applying device 201 may apply two types of liquid that react with each other on the substrate 11 to increase adhesion. Examples of materials to which the first particles P1 can be attached include resins such as acrylic resins.

[0139] The powder applying device 202 applies a powder containing the first particles P1 to the substrate 11 on which the liquid has been arranged in a pattern. As a result, the first particles P1 are fixed by the material on the substrate 11, and the first particles P1 are fixed in a pattern corresponding to the pattern L1.

[0140] The means for applying the powder by the powder applying device 202 may be a means for spraying or sprinkling the powder toward the substrate 11. The powder applying device 202 may further include a means for removing the first particles P1 that are not fixed to the substrate 11 by means of vibration, centrifugation, air blowing, suction, or the like.

[0141] The particle arrangement device 2 may further include a drying device that evaporates at least a part of the liquid applied by the liquid application device 201 to control the amount of material on the substrate 11, the thickness of the pattern L1, and the like. This drying device may be provided downstream of the liquid application device 201 and upstream of the powder application device 202. The material on the substrate after drying may be a liquid, a liquid containing solids, or only solids.

[0142] In the manufacturing method of the electrode substrate, the second step can be said to be a particle rubbing step in which the first particles P1 arranged on the surface of the adhesive portion are fixed by rubbing. In the particle rubbing step, the first particles P1 are rubbed using the above-mentioned support material S3. The manufacturing method of the electrode substrate may include the above-mentioned steps, and the order of the steps may be changed as appropriate. For example, after the step of disposing the first particles P1 on the resin substrate, a step of rubbing the surfaces of the first particles P1 is performed. After the rubbing step, a step of disposing the second particles P2 on the resin substrate is performed. Furthermore, a step of rubbing the first particles P1 and the second particles P2 may be performed. That is, the particle rubbing step may include a step of rubbing the first particles P1 and the second particles P2 disposed on the resin substrate.

[0143] 12 is a diagram showing a schematic diagram of each device in the second step and the third step. The substrate 11 on which the first particles P1 are arranged is transferred to the belt device in FIG. The belt device is provided with a particle rubbing device 25 on the upstream side and a filling device 24b for disposing the second particles P2 downstream. The particle rubbing device 25 has pressure rollers 223c and 223d, and the pressure roller 223d rotates by being driven. At least one of the pressure rollers 223c and 223d is preferably a soft roller having an elastic layer on its surface, for example, a soft roller having an elastic layer of silicone rubber or fluororubber on the surface of a stainless steel core metal. In addition, a heater (not shown) may be built into at least one of the pressure rollers 223c and 223d.

[0144] The substrate 11 is conveyed to the pressure section between the pressure rollers 223c and 223d by the belt device. When the substrate 11 is pressed by the pressure rollers 223c and 223d, the first particles P1 arranged on the surface of the adhesive portion on the substrate are precipitated to the adhesive portion on the substrate. At this time, the above-mentioned heater may be used to facilitate rearrangement of the particles in the adhesive portion on the substrate. In addition, a heating source may be provided upstream of the particle rubbing device 25 to heat the adhesive portion on the substrate.

[0145] Since the pressure roller 223c comes into contact with the particle layer 12 on the substrate, it is preferable to coat the surface with a material having good releasability, such as fluorine, in order to suppress adhesion of particles. A cleaning mechanism for removing particles adhering to the pressure roller 223c may be provided. It is more preferable to apply pressure to the particle layer 12 while it is covered with a protective material (not shown). In this case, the protective material used is preferably a material with good releasability, and if it is resin, it is preferably a fluorine sheet, if it is metal, it is preferably nichrome foil, etc. When using a protective material, a removal mechanism (not shown) for removing the protective material is provided downstream of the particle rubbing device 25 and upstream of the second filling device 24b.

[0146] The particle rubbing device 25 may be any other known pressurizing device, such as an isostatic pressurizing device (CIP / HIP), a uniaxial pressurizing device, or a device that uses a weight or a magnet.

[0147] After the first particles P1 arranged on the substrate 11 are rubbed and fixed, a liquid may be applied by a liquid applying device 203 to provide an adhesive portion at least in the area where the first particles P1 were not arranged. The liquid applying device 203 has the same function as the liquid applying device 201. In addition, a removal mechanism (not shown) for removing excess solvent from the applied liquid may be provided. The second particles P2 are arranged on the surface of the substrate 11 to which the liquid has been applied by the liquid applying device 203, using a second filling device 24. As a result, a dense particle layer 12 is formed on the substrate 11.

[0148] Similarly to the particle arrangement device 1, the particle arrangement device 2 may have a transfer unit. In this case, the transfer unit is provided downstream of the powder applicator 202. The first particles P1 are transferred from the substrate 11 to another substrate having an adhesive portion. In the substrate to which the first particles P1 have been transferred, the second particles P2 can be arranged by using the second filling device 24 in the region where the first particles P1 are not arranged and the adhesive portion is exposed. This makes it possible to arrange the first particles P1 and the second particles P2 densely on the adhesive portion of the resin substrate.

[0149] Using the above-mentioned particle arrangement device 1 or particle arrangement device 2, first particles P1 are arranged on the adhesive portion of the resin substrate in the first step (S101 in FIG. 2) of FIG. 2, the first particles P1 are rubbed and fixed in place in the second step (S103 in FIG. 2) of FIG. 2, and second particles P2 are arranged on the adhesive portion of the resin substrate in the third step (S103 in FIG. 2).

[0150] A simple device that does not use a belt device can be used as the first and second filling devices 24. Fig. 13 shows an example of the device. The third filling device 24 has a filling container 242, a stirring screw member 243, a magnetic member 247, a magnet 248, and a regulating member 250. 14 is a schematic diagram illustrating the operation of the filling device. Filler 241 sufficiently stirred by stirring screw member 243 is supplied in an appropriate amount by magnetic member 247 (arrow a in the figure) that has moved from the home position and by regulation by regulating member 250. The supplied filler 241 is rubbed on substrate 11 with the reciprocating movement of magnetic member 247 (arrow b in FIG. 14). After rubbing a desired number of times, the magnetic member 247 moves to a distant home position where the magnetic force acting on the filler 241 on the substrate is sufficiently weakened (arrow c in FIG. 14). The filler 241 on the substrate falls downward by gravity and is collected in a collection container (not shown). At this time, it is more preferable to use air blowing or vibration. Also, instead of rubbing on an inclined surface as shown in the figure, rubbing on a flat surface may be performed to collect the filler 241, and then the magnetic member 247 may again move back and forth to collect the filler 241 remaining on the substrate. At this time, it is more preferable to use air blowing or vibration during each collection.

[0151] In the preparation of the electrode substrate, an additional step may be added between the steps described above or after step 3. That is, a step of arranging the third particles P3 and a step of rubbing the arranged third particles P3 may be added. For example, after the step of disposing first particles P1 on a resin substrate, a step of rubbing the surfaces of the first particles P1 is performed. After the rubbing step, a step of disposing second particles P2 on the resin substrate is performed. Then, a step of disposing third particles P3 on the first particles P1 and the second particles P2 may be performed. Furthermore, a step of rubbing the surfaces of the third particles P3 may be performed. When the third particles P3 are applied, they can be applied in the same manner as the filling devices 24a and 24b described in the particle arrangement device 1 or the mechanism described in the particle arrangement device 2. In addition, the rubbing step can also be performed after the arrangement of each particle by using the magnetic particles and the rubbing device described above.

[0152] In the electrode substrate, the coverage rate of the resin substrate surface by the active material particles and solid electrolyte particles is preferably 60% or more, more preferably 70% or more, and even more preferably 80% or more. In the present disclosure, the coverage rate of the resin substrate surface refers to the ratio (area %) of the area covered by the active material particles and solid electrolyte particles to the entire area of ​​the resin substrate surface. The coverage rate of the substrate surface by the active material particles and solid electrolyte particles can be measured by photographing the area where the particle layer is formed using an optical microscope from the substrate vertical direction, and calculating the area ratio of the area covered by the active material particles and solid electrolyte particles using image processing software. The measurement method will be described in detail later.

[0153] The upper limit of the coverage is not particularly limited, but is preferably 99% or less, and more preferably 98% or less. For example, the coverage of the resin substrate surface by the active material particles and solid electrolyte particles is preferably 60 to 99%, 70 to 99%, 80 to 99%, or 60 to 98%, 70 to 98%, or 80 to 98%. When the coverage rate is within the above range, a dense particle layer is formed on the substrate, and the denseness of the particles in the electrode can be improved, resulting in improved ion conductivity.

[0154] <Electrode manufacturing method> An example of a method for manufacturing an electrode will be described in detail below with reference to the drawings. Although a positive electrode using a lithium secondary battery will be described as an example, the manufacturing method described below can be used as a manufacturing method for electrodes regardless of whether they are positive electrodes or negative electrodes.

[0155] The method for producing an electrode includes the following three steps (first step, second step, and third step). (1) The first step of laminating a plurality of electrode substrates to form a laminate (S201 in FIG. 15) (2) A second step (S202 in FIG. 15) of removing the resin substrate from the laminate to obtain a three-dimensional object; (3) A third step (S203 in FIG. 15) of applying pressure to the three-dimensional object to obtain an electrode.

[0156] That is, the electrode is an electrode manufactured by a manufacturing method including a step of laminating a plurality of electrode base materials and forming a laminate, a step of removing the resin base material from the laminate to obtain a three-dimensional object, and a step of pressing the three-dimensional object. For example, a sintered body of the above-mentioned electrode base material can be used as the electrode. Each step of the electrode manufacturing method will now be described in detail.

[0157] (1st step) The first step is a step of laminating a plurality of electrode base materials to form a laminate. The number of layers is not particularly limited and is determined according to the desired electrode capacity. For example, it is preferable to laminate three or more of the above-mentioned electrode base materials. In addition, the electrode base materials to be laminated may be the same, or different electrode base materials may be laminated.

[0158] That is, the electrode substrate can also be used as an electrode substrate laminate in which a plurality of electrode substrates are laminated. As described above, the electrode substrate has a resin substrate and a particle layer formed on the resin substrate. When laminating the electrode substrates, it is preferable to laminate the electrode substrates so that the electrode substrate laminate has the resin substrate and the particle layer alternately. That is, it is preferable that the electrode substrate laminate has a configuration in which the resin substrate and the particle layer alternate in the cross section of the electrode substrate laminate. Such a configuration allows sufficient contact between the active material particles, between the active material particles and the solid electrolyte particles, and between the solid electrolyte particles, thereby further improving ionic conductivity and electronic conductivity. For example, a sintered body of the electrode substrate laminate can be used as an electrode. Also, a sintered body obtained by sintering an electrode substrate, in which at least a part of the resin substrate in the electrode substrate has been removed, may be used as an electrode.

[0159] In addition, the laminate is preferably formed on an electrode current collector as a substrate. That is, the electrode preferably has a substrate. As the electrode current collector, a known current collector such as Al foil, SUS foil, Cu foil, Cu-Ni foil, platinum foil, or gold foil can be used. An electrolyte may be used as the substrate. As described above, the contact area between the active material particles having excellent electronic conductivity and the current collector can be increased to facilitate smooth electron transfer. Therefore, it is preferable that the surface of the electrode substrate on which the active material particles are largely exposed is provided on the current collector side. In other words, when forming the laminate on the electrode current collector, it is preferable to laminate the electrode substrate so that the surface on the resin substrate side is provided on the current collector side.

[0160] In this case, the electrolyte may be a separately prepared solid electrolyte sheet or an electrolyte substrate consisting of only solid electrolyte particles on a similar substrate. That is, a solid electrolyte may be used as the electrolyte. In addition, the solid electrolyte sheet or electrolyte substrate may have a negative electrode or a negative electrode substrate formed on the opposite side to the lamination surface of the positive electrode substrate.

[0161] 16 is a diagram showing a schematic configuration of a laminate forming apparatus. The laminate forming apparatus has a conveying device 31 that conveys a substrate 11 on which a particle layer 12 is formed, and a stage 32 that can be moved forward and backward in the vertical direction by an actuator (not shown).

[0162] The conveying device 31 receives the substrate 11 having the particle layer 12 formed using the particle arrangement device, and conveys it to the stage 32. Examples of the conveying device 31 capable of conveying the substrate 11 include a belt conveyor, a roller, and a robot arm. When the substrate 11 is transported to the stage 32 by the transport device 31, the stage 32 moves in the vertical direction by an amount equivalent to the thickness of the substrate 11 and the particle layer 12. By repeating the transport by the transport device 31 and the movement of the stage 32, a plurality of substrates 11 each having a particle layer 12 formed thereon are stacked, and the laminate 15 is formed.

[0163] In this case, it is preferable that the back surface of the substrate 11 on which the particle layer 12 is formed has an adhesive portion. This adhesive portion allows the substrates to adhere to each other, increasing the strength of the laminate and suppressing misalignment between the substrates even after the first step. Furthermore, the particle layer 12 between the substrates is sandwiched between the upper and lower adhesive portions, thereby suppressing misalignment during processing or storage of the laminate. The adhesive portion may be applied by a coating device (not shown) before lamination, or a substrate that has been previously coated may be used, and the protective film coated on the coated surface may be peeled off before lamination to laminate.

[0164] It is preferable to have a static elimination step of eliminating static electricity from the substrate immediately before forming the laminate 15. The particle layer 12 and substrate 11 formed using the particle arrangement device are easily charged, and electrostatic repulsion occurs between the substrates when they are laminated. Therefore, when they are laminated in the first step, the substrates tend to peel off or gaps tend to form between the substrates. In the static elimination step, it is preferable to eliminate static electricity in a non-contact manner using a static elimination blower or the like. In addition, after the laminate 15 is formed, it is preferable to have a degassing step of degassing the laminate in order to reduce voids between the substrates. In the degassing step, degassing is preferably performed using a vacuum packaging machine or the like.

[0165] (2nd process) The second step is a step of sintering the laminate to remove the resin substrate from the laminate. 17 is a diagram showing a schematic configuration of a sintering apparatus, which includes a transport device 41 for transporting the laminate 15 and a heating furnace 42 for heating the laminate 15.

[0166] The conveying device 41 receives the laminate 15 from the laminate forming device and conveys it to the heating furnace 42. Like the conveying device 31, the conveying device 41 is preferably a device capable of conveying the laminate 15. Examples of devices capable of conveying the laminate 15 include a belt conveyor, a roller, and a robot arm.

[0167] The heating furnace 42 is a furnace that heats the laminate 15. The heating furnace 42 has a heating means 421, a pressurizing means 422, and an atmosphere adjusting means 423. A firing furnace used for firing ceramics or the like can be used as the heating furnace 42. The pressurizing means 422 pressurizes the laminate 15 that is being heated in the heating furnace 42, and pressurizes the laminate 15 before and after heating.

[0168] In addition, it is preferable that the pressurizing means 422 has a pressurizing portion for pressurizing the laminate 15 formed of a porous material that allows easy passage of gas. The atmosphere adjusting means 423 has an atmosphere gas supplying means 423a and a pressure reducing means 423b, and adjusts the atmosphere gas in the processing space of the heating furnace 42. The atmospheric gas that can be used includes an oxidizing atmosphere (O2), an inert atmosphere (Ar, N2, etc.) and a reducing atmosphere (Ar-H2), but sintering may be performed in air.

[0169] When the laminate is sintered, it is preferable to heat the laminate at a temperature equal to or higher than the thermal decomposition temperature of the substrate 11 in the laminate 15, and preferably at a temperature lower than the thermal decomposition temperature of each particle layer in the laminate 15. The temperature at which the laminate is heated is preferably 200° C. or higher and 1000° C. or lower. The sintering temperature is preferably maintained for 30 minutes or more, and more preferably for 1 hour or more. The thermal decomposition temperature is the temperature at which the weight of the material starts to decrease when the temperature is gradually increased in the heating atmosphere in the sintering treatment device. Therefore, by heating the laminate at a temperature equal to or higher than the thermal decomposition temperature of the base material 11, the base material 11 in the laminate can be decomposed to reduce its weight, and the resin base material can be removed from the laminate.

[0170] The heating temperature is preferably equal to or higher than the thermal decomposition temperature of the base material 11, but it is preferable to heat the base material 11 at a temperature higher than the thermal decomposition temperature. Specifically, when the base material 11 is heated from room temperature (25°C) at a rate of 5°C / min in an atmosphere (typically air) during heating in a sintering treatment device and a thermogravimetric analysis is performed, the base material 11 is preferably heated at a temperature equal to or higher than the temperature at which the mass becomes 70% by mass of the initial mass. Specifically, the temperature is preferably 385°C or higher, for example.

[0171] Similarly, when a thermogravimetric analysis is performed, it is more preferable to heat at a temperature equal to or higher than the temperature at which the mass is reduced to 50% by mass of the initial mass, and even more preferable to heat at a temperature equal to or higher than the temperature at which the mass is reduced to 20% by mass of the initial mass. Specifically, for example, it is preferable to heat at a temperature equal to or higher than 400°C, and more preferably equal to or higher than 450°C. This can shorten the time required to remove the resin substrate and increase the removal rate of the resin substrate.

[0172] In this way, when the sintering treatment apparatus removes the base material 11 by heating, it is preferable that the active material particles and the solid electrolyte particles have a higher thermal decomposition temperature than the base material 11. In general, inorganic materials tend to have higher thermal decomposition temperatures than organic materials, so it is preferable that the active material particles and the solid electrolyte particles are inorganic materials and the material of the base material 11 is an organic material such as a resin. In addition, when the sintering treatment apparatus removes the base material 11 by heating, it is preferable that the active material particles have a softening point temperature higher than the thermal decomposition temperature of the base material 11.

[0173] The sintering apparatus is required to remove at least a part of the resin substrate in the laminate 15 by heating, and provide a portion where the particles of the upper and lower layers of the laminate contact each other. It is preferable to eliminate 90% by mass or more of the resin substrate in the laminate 15, more preferably 95% by mass or more, and even more preferably 97% by mass or more. At that time, it is preferable that the resin substrate is burned or gasified and released to the outside as a gas. At this time, when the resin substrate gasified by pyrolysis is released to the outside of the laminate as a gas, it may push up the particle layer formed on the resin substrate, causing the shape to be disturbed. For this reason, it is preferable to reduce the thickness of the resin substrate to reduce the effect on the particle layer.

[0174] Specifically, the thickness (μm) of the resin substrate is preferably 10 times or less, more preferably 5 times or less, and even more preferably 2 times or less, the thickness of the particle layer on the resin substrate. Here, the thickness of the particle layer refers to the difference between the maximum and minimum values ​​of z in the region (x, y, z) where each particle arranged on the resin substrate exists, when the resin substrate surface is (x, y) and the lamination direction of the resin substrate is (z) in the electrode substrate. The thickness of the resin substrate is preferably 1 μm or more and 1 mm or less, and the thickness of the particle layer is preferably 0.1 μm or more and 100 μm or less.

[0175] The thickness of the particle layer on the resin substrate is calculated by observing the cross section of the laminate 15 with a BIB-SEM, determining the particle presence area (x, z) with image processing software, and calculating the difference between the maximum and minimum values ​​of z, where x is the resin substrate surface and z is the lamination direction of the resin substrate. Here, the BIB-SEM photographing conditions, the necessary image area, and the image processing method are the same as those described above.

[0176] The thickness of the resin substrate may be determined by BIB-SEM in the same manner as the particle diameter of the active material particles. The thickness may be measured using a gauge such as a thickness gauge. In addition, in SEM observation using a BIB-SEM, the active material particles, solid electrolyte particles, substrate, and adhesive portion may be identified by elemental composition analysis using EDS.

[0177] The sintering apparatus preferably exhausts the released gas to the outside of the heating furnace 42 using the pressure reducing means 423b. The resin base material can be burned and removed by creating an oxidizing atmosphere, i.e., an atmosphere containing oxygen gas such as air, inside the heating furnace 42 using the atmospheric gas supplying means 423a or the like. On the other hand, depending on the active material particles and solid electrolyte particles used, sintering in an oxidizing atmosphere may cause decomposition or composition change. In such cases, sintering in an inert atmosphere (Ar, N2, etc.) or a reducing atmosphere (Ar-H2) is preferable. stomach.

[0178] As described above, when the resin base material is gasified by pyrolysis from the laminate 15 and released as a gas, each particle layer in the laminate 15 may be pushed up and change shape. Therefore, when heating in the heating furnace 42, the laminate 15 may be pressurized by the pressurizing means 422 before or during heating.

[0179] FIG. 18A is a BIB-SEM image of the cross section of the laminate after the first step. The laminate 15 is formed by laminating six second base materials 11b, each having a particle layer 12 formed thereon, on a substrate 14. FIG. 18B is a BIB-SEM image of a three-dimensional object 16 (positive electrode) after the second step. The resin base material has been removed from the laminate 15, resulting in a three-dimensional object 16 consisting of six particle layers. FIG. 18C is an SEM image of the upper part of the three-dimensional object 16. The first particles P1 and the second particles P2 periodically arranged on the second base material 11b in the first step are maintained even after the second step.

[0180] (3rd step) The third step is a step of pressing the three-dimensional object 16 from which the resin base material has been removed. As a method of applying pressure, the three-dimensional object 16 can be pressed by the pressurizing means 422 during cooling or heat dissipation after heating. Alternatively, after removing the resin base material by a sintering treatment device, pressure can be applied by a separate pressurizing device. Specific pressing methods are preferably vacuum degassing, isostatic pressing, or a general hydraulic press or roller press. Among them, pressing by a combination of vacuum degassing and isostatic pressing is preferable.

[0181] The pressure is preferably 5 MPa to 500 MPa. This fills the voids in the three-dimensional object from which the resin base material has been removed, improving the density and strength of the three-dimensional object. After the third step, the three-dimensional object may be heated again in a sintering device for sintering. Alternatively, the laminate may be permeated with a solution in which a conductive additive, a binder resin, etc. are dispersed in a solvent, and each material may be dispersed within the laminate.

[0182] An electrode can be manufactured by a manufacturing method including the above-mentioned steps. The electrode preferably has a substrate and a particle layer containing active material particles and solid electrolyte particles, and preferably has voids in the particle layer. With this configuration, it is possible to improve ion conductivity in the electrode and reduce volumetric fluctuations of the active material particles.

[0183] 19 is a diagram showing a schematic diagram of an overall configuration of an additive manufacturing system 100. The additive manufacturing system 100 includes a control unit U1, a particle layer forming unit U2, a lamination unit U3, a removal unit U4, and a post-processing unit U5.

[0184] The control unit U1 is responsible for controlling each part of the additive manufacturing system 100. In the particle layer forming unit U2, the above-mentioned particle placement device (FIG. 3) is used to deposit particles on the substrate 11. Layer 12 is formed. The lamination unit U3 uses the laminate molding apparatus described above (Figure 16) to laminate multiple substrates 11, each of which has a particle layer 12 formed thereon in the particle layer forming unit U2, to form a laminate 15 including multiple particle layers 12 and multiple substrates 11. The removing unit U4 uses the above-mentioned sintering treatment device (FIG. 17) to remove the base material 11 from the laminate 15 formed in the lamination unit U3 to form a three-dimensional object 16 (electrode). The post-processing unit U5 performs post-processing of the three-dimensional object 16 formed by the removal unit U4. 19 is merely an example, and other configurations may be used. The configuration and operation of each unit will be described below.

[0185] [Control unit] The control unit U1 is responsible for controlling each part of the additive manufacturing system 100, specifically, the particle layer forming unit U2, the stacking unit U3, the removing unit U4, and the post-processing unit U5. The control unit U1 may include a three-dimensional shape data input unit that receives input of three-dimensional shape data of a three-dimensional object (hereinafter, sometimes referred to as a "modeling target") to be formed by the additive manufacturing system 100 from an external device (e.g., a personal computer, etc.). As the three-dimensional shape data, data created and output by a three-dimensional CAD, a three-dimensional modeler, a three-dimensional scanner, etc. can be used. The file format is not important, but for example, an STL (StereoLithography) file format can be preferably used.

[0186] The control unit U1 may be equipped with a slice data calculation section that slices the three-dimensional shape data at a predetermined pitch to calculate the cross-sectional shape of each layer, and generates image data (referred to as "slice data") to be used for image formation in the particle layer forming unit U2 based on the cross-sectional shapes.

[0187] Although the details will be described later, the particle layer forming unit U2 of this embodiment can use a plurality of types of materials to form a material layer in which each material is patterned. Therefore, data corresponding to the image of each material may be generated as slice data. As a file format for slice data, for example, multi-value image data (each value represents a type of material) or multi-plane image data (each plane corresponds to a type of material) can be used.

[0188] Although not shown, the control unit U1 also includes an operation unit, a display unit, and a memory unit. The operation unit has a function of receiving instructions from the user. For example, it is possible to input power on / off, various settings of the device, and operation instructions. The display unit has a function of presenting information to the user. For example, it is possible to present various setting screens, error messages, operation status, and the like. The memory unit has a function of storing three-dimensional shape data, slice data, various setting values, and the like.

[0189] In terms of hardware, the control unit U1 can be configured by a computer equipped with a CPU (Central Processing Unit), memory, auxiliary storage device (hard disk, flash memory, etc.), input device, display device, and various I / Fs. Each of the above-mentioned functions is realized by the CPU reading and executing a program stored in the auxiliary storage device or the like, and controlling the necessary devices. However, some or all of the above-mentioned functions may be configured by circuits such as ASIC or FPGA, or may be executed by another computer using technologies such as cloud computing or grid computing.

[0190] [Particle layer formation unit] The particle layer forming unit U2 is a unit that forms a particle layer 12 on the substrate 11. The particle arrangement device (FIG. 3) described above can be used as the particle layer forming unit U2. The particle layer forming unit may have a particle filling unit and a rubbing unit. The additive manufacturing system 100 may have a plurality of particle layer forming units U2. This allows the particle layers 12 to be formed on the substrate 11 in parallel at the same time, and the throughput of forming the laminate and the three-dimensional object can be further improved. In addition, when there are many types of materials constituting the three-dimensional object, it is possible to omit switching of the material type and process in the particle layer forming unit U2 by providing a particle layer forming unit U2 for each material type or for each group of material types. This allows the three-dimensional object to be manufactured continuously.

[0191] [Stacked unit] The lamination unit U3 is a unit that laminates a plurality of base materials 11 on which a particle layer 12 has been formed in the particle layer forming unit U2, to form a laminate 15 including a plurality of particle layers 12 and a plurality of base materials 11. The laminate forming apparatus (FIG. 16) described above can be used. The lamination unit U3 may further include a conveying device 33 that conveys the formed laminate 15 to the removal unit U4 or the like, and a pressurizing device (not shown) that pressurizes the laminate 15 in the lamination direction. The conveying device 33 may have a configuration similar to that of the conveying device 31.

[0192] [Removal unit] The removing unit U4 is a unit that removes the base material 11 from the laminate 15 formed in the lamination unit U3 to form a three-dimensional object 16. The above-mentioned sintering treatment device (FIG. 17) can be used.

[0193] [Post-processing unit] The post-processing unit U5 is a unit that performs post-processing of the three-dimensional object 16 formed by the removal unit U4. The type of post-treatment performed by the post-treatment unit U5 is not particularly limited, but may be, for example, a process of further heating and sintering the three-dimensional object 16. When the post-treatment unit U5 performs a heat treatment as a post-treatment, the removal unit U4 may also have that function. By sintering the three-dimensional object 16, the particles in and between each particle layer can be sintered.

[0194] In addition, depending on the active material particles and solid electrolyte particles used, reducing gas such as carbon monoxide generated when the resin base material disappears may change the composition and reduce the ion conductivity. In that case, the composition can be changed again by sintering (oxidation) in the post-treatment unit U5 to improve the ion conductivity. Of course, in the sintering in the post-treatment unit U5, sintering may be performed in an inert atmosphere such as Ar or N2 or a reducing atmosphere such as ArH2, other than an oxidizing atmosphere with a controlled oxygen concentration.

[0195] As an example of a post-treatment other than sintering, a solution in which a conductive assistant, a binder resin, etc. are dispersed in a solvent is impregnated into the laminate, and each material is dispersed in the laminate. After dispersion, a drying process or a pressurizing process may be included to volatilize the solvent and fix the binder.

[0196] A secondary battery has electrodes (positive and negative electrodes), an electrolyte layer adjacent to the electrodes, and, if necessary, a current collector. For example, an electrode manufactured using the above-mentioned electrode base material can be used as the positive electrode. The electrode can be manufactured, for example, by the above-mentioned method. The negative electrode can be made of any known material without any particular limitation, such as a metal foil forming a lithium alloy layer, such as lithium metal, indium, tin, aluminum, zinc, or magnesium, or a negative electrode containing graphite particles (such as graphite, hard carbon, or soft carbon), silicone particles, or lithium titanate particles.

[0197] The electrolyte layer is not particularly limited and any known material can be used. For example, , Li 1.5 Al 0.5 Ge 1.5 P3O 12 (hereinafter referred to as LAGP), Li 1.3 Al 0.3 Ti 1.7 P3O 12 (hereinafter referred to as LATP), Li 5.9 Yb 0.81 La 0.09 Zr 0.1 (BO3)3 (hereinafter also written as LYbBO), Li3BO3 (hereinafter also written as LBO), Li 6.25 La3Zr2Al 0.25 O 12 (hereinafter referred to as LLZ), Li 0.33 La 0.55 The electrolyte may be an electrolyte sheet made by pelletizing the material with a pressurizing device and sintering it. The current collector is not particularly limited and may be any known material. For example, aluminum, stainless steel, platinum, gold, etc. may be used as the positive electrode current collector. Copper, copper nickel, platinum, gold, etc. may be used as the negative electrode current collector. The above metals that can be used as the current collector may be used as metal foil.

[0198] <Secondary battery manufacturing method> There are multiple possible methods for manufacturing secondary batteries using the above-mentioned additive manufacturing system 100, but several examples will be given below. A case where the system is used to manufacture a positive electrode or a negative electrode will be described. Using a current collector or an electrolyte formed by a different means as a base, the system can manufacture a positive electrode, a negative electrode, or both electrodes.

[0199] The secondary battery can be manufactured by stacking the electrodes, the current collectors, and the electrolyte, packaging the stack with an aluminum laminate film or the like as necessary, and molding and pressing the stack. That is, the manufacturing method of the secondary battery may include a step of stacking the electrodes, the current collectors, and the electrolyte. The electrodes may be the above-mentioned electrodes. The method for producing a secondary battery may include a step of preparing an electrode by the above-mentioned electrode production method, and a step of providing a solid electrolyte adjacent to the electrode. The method may also include a step of providing the above-mentioned electrode and the solid electrolyte adjacent to the electrode together. That is, the electrode and the solid electrolyte may be prepared in separate steps, or may be prepared together in the same step.

[0200] Here, the other means for forming the electrolyte is a known means, for example, forming solid electrolyte particles into pellets using a uniaxial pressurizing device or the like, and sintering them in an electric furnace, etc. The electrolyte may be an electrolyte sheet or the like. By stacking the manufactured components in the order of positive electrode current collector, positive electrode, electrolyte, negative electrode, and negative electrode current collector, it is possible to manufacture a laminate-type secondary battery to be packed in a laminate film or a coin-type secondary battery to be packed in a coin case.

[0201] The particles constituting the positive electrode, electrolyte, and negative electrode may have different appropriate temperatures and atmospheres during sintering. When handling such materials, it is preferable to separately manufacture the positive electrode, electrolyte, and negative electrode, which are the respective components, and assemble them into a battery. When lithium metal or indium is used as the negative electrode, it is preferable to use the negative electrode as a metal foil or to form it into a current collector or electrolyte by a vacuum process such as sputtering. Since lithium metal has a strong reducing power, it is easily decomposed depending on the type of solid electrolyte. In that case, a buffer layer may be provided between the electrode and the electrolyte. As the buffer layer, it is preferable to use a polymer electrolyte or the like.

[0202] The above example is an example in which a positive or negative electrode laminate is formed and an electrode is manufactured using the additive manufacturing system 100, but it is also possible to form a laminate containing two or more of the main components of a secondary battery, namely a positive electrode collector, a positive electrode, an electrolyte, a negative electrode, and a negative electrode collector, and manufacture it as a three-dimensional object.

[0203] For example, each of the substrates is prepared by the particle layer forming unit U2. That is, the substrates are a positive electrode current collector substrate, a positive electrode substrate, an electrolyte substrate, a negative electrode substrate, and a negative electrode current collector substrate. Each substrate may contain multiple types of particles (positive electrode active material particles and solid electrolyte particles) like the positive electrode substrate, or may contain only a single type of particle. When only a single type of particle is contained, the substrate is filled with the filling device 24a. , 24b are filled with the same type of filler, it is possible to form a dense particle layer containing only a single type of particle on the substrate.

[0204] The electrolyte base material is formed of a particle layer containing at least solid electrolyte particles. The negative electrode base material is formed of a particle layer containing at least negative electrode active material particles. The current collector base material is formed of a particle layer containing at least conductive particles. These base materials are stacked in the order of positive electrode current collector base material, positive electrode base material, electrolyte base material, negative electrode base material, and negative electrode current collector base material by the stacking unit U3 to produce a stack, and a secondary battery can be manufactured by the removal unit U4 and the post-treatment unit U5. Furthermore, it is also possible to manufacture a bipolar type secondary battery in which electrode base materials are stacked on both sides of the current collector base material. EXAMPLES

[0205] The present invention will be described in more detail below using examples, but the present invention is not limited to these examples. In the following examples, unless otherwise specified, the parts are based on parts by weight.

[0206] The above-described additive manufacturing system 100 was used to mold a positive electrode of a secondary battery. Specifically, a particle layer was formed on a resin substrate using the particle layer forming unit U2 shown in Fig. 19, and the substrate on which the particle layer was formed was laminated (three laminates) on a current collector (Al foil) using the lamination unit U3 to form a laminate. The method of applying particles using the particle layer forming unit U2 was selected from methods 1 to 4 shown in Fig. 20 and used as shown in Table 1 below. Thereafter, the resin substrate was removed from the laminate by heating using the removal unit U4, and the laminate was pressed to form a three-dimensional positive electrode. The sintering atmosphere and sintering temperature (maintained for 1 h) were as shown in Table 5 below.

[0207] The electrolyte is Li 1.5 Al 0.5 Ge 1.5 P3O 12 The electrolyte sheet (thickness 260 μm) was made by pelletizing the powder (hereinafter referred to as LAGP) using a uniaxial press and sintering it in an electric furnace (850 °C / 12 h). The negative electrode was indium foil (thickness 50 μm). An aluminum foil (thickness: 20 μm) was used as the positive electrode current collector, and a copper foil (thickness: 20 μm) was used as the negative electrode current collector. The above-mentioned materials were laminated in the order of positive electrode current collector, positive electrode, electrolyte, negative electrode, and negative electrode current collector, and packed in an aluminum laminate film so that the tab lead for the extraction electrode, which had been welded to the current collector in advance, was positioned outside the laminate. The resultant was then molded into a laminate cell type using a vacuum packaging machine, and pressed (196 MPa) using an isostatic pressure pressurizing device to produce an all-solid-state secondary battery.

[0208] A polyester (PET) sheet was used as the first base material 11a. A honeycomb-shaped concave-convex pattern was formed on the first base material 11a by a pattern forming device . First, an ultraviolet-curable resin (ultraviolet-curable liquid silicone rubber, PDMS, manufactured by Shin-Etsu Chemical Co., Ltd.) was applied onto the first base material 11a. Then, a film mold (standard mold, manufactured by Soken Chemical & Engineering Co., Ltd.) having a honeycomb-shaped concave-convex pattern on its surface corresponding to the concave-convex pattern to be formed was pressed against the ultraviolet-curable resin on the first base material 11a. With the film mold pressed against it, ultraviolet rays were irradiated from a UV lamp to cure the ultraviolet-curable resin, and the film mold was released.

[0209] The structure of the first base material 11a having a concave-convex pattern 111a formed on its surface is shown in Figures 21A and 21B. Figure 21A is a top view of the first base material 11a, and Figure 21B is a cross-sectional view taken along line AA in Figure 21A. As shown in Figures 21A and B, a honeycomb-shaped concave-convex pattern having hexagonal frame-shaped convex portions is formed on the surface of the first base material 11a. 21B, the width of adjacent convex portions is k (μm), the pitch of adjacent convex portions is s (μm), and the height of a convex portion is d (μm). In the following examples, the shape of the concave-convex pattern was measured using a non-contact surface / layer cross-sectional shape measurement system (VertScan2.0 manufactured by Ryoka Systems Co., Ltd.).

[0210] As the second base material 11b, a polyester (PET) sheet with an acrylic adhesive applied to the front and back sides was used. The thickness of the second base material 11b used was 3 μm. The acrylic adhesive was applied to the front and back sides of the second base material 11b to form an adhesive portion. The thickness of the formed adhesive portion was 1 μm.

[0211] The first particles P1 are active material particles, such as LiCoO2 (hereinafter also referred to as LCO), LiMO2 (M is an element selected from the group consisting of Ni, Mn, and Co. Hereinafter also referred to as NMC), LiFePO4 (hereinafter also referred to as LFP), or Li3V2(PO4)3 (hereinafter also referred to as LVP). The second particles P2 are solid electrolyte particles, such as Li3BO3 (hereinafter also referred to as LBO), Li 5.9 Yb 0.81 La 0.09 Zr 0.1 (BO3)3 (manufactured in-house; hereafter also referred to as LYbBO). Note that LCO was manufactured by Nippon Chemical Industry Co., Ltd. (CellSeed C-5H), NMC was manufactured by Nippon Chemical Industry Co., Ltd. (CellSeed NMC), LFP was manufactured by Toshima Manufacturing Co., Ltd., LVP was manufactured by Tokyo Chemical Industry Co., Ltd., and Li3BO3 was manufactured by Toshima Manufacturing Co., Ltd.

[0212] The carrier S1 for the first particles P1, the carrier S2 for the second particles P2, the carrier S3 for the third particles P3, and the particles S0 used for rubbing are all magnetic particles, i.e., standard carriers (manufactured by the Imaging Society of Japan). A standard carrier P02) was used. The cumulative 50% particle size (median diameter) in the volume-based particle size distribution of the standard carrier was 81 μm.

[0213] <Method of manufacturing electrode substrate 1> LCO (first particles P1) and LBO (second particles P2) were mixed at a volume ratio of 7:3 to obtain a mixed powder. The obtained mixed powder and a standard carrier (support material S1) were stirred and mixed to obtain a filler 241a. The above volume ratio was equivalent to the ratio of LCO and LBO applied to the electrode substrate 2 used in Example 1 below. The method for forming the particle layer was the method 1 shown in FIG. 20A. Using the obtained filler 241a, a particle layer 1 was formed on the resin substrate by the particle layer forming unit U2 to obtain an electrode substrate 1. That is, an electrode substrate 1 was obtained in which the LCO and LBO contained in the mixed powder as the first particles P1 and the second particles P2 were arranged on the resin substrate. At this time, the concave-convex pattern 111a on the first substrate 11a was controlled so that the width k of the concaves was 6.0 μm, the pitch s of the convexities was 7.5 μm, and the height d of the convexities was 5.5 μm. The obtained electrode substrate 1 was designated Comparative Example 1.

[0214] <Method of manufacturing electrode substrate 2> LCO (first particles P1) and a standard carrier (support S1) were stirred and mixed to obtain a filler 241a. In a similar manner, LBO (second particles P2) and a standard carrier (support S2) were stirred and mixed to obtain a filler 241b. Using the obtained fillers 241a and b, a particle layer 2 was formed on the resin substrate by the particle layer forming unit U2 to obtain an electrode substrate 2. The particle layer was formed by the method 1 shown in FIG. 20A. That is, the obtained filler 241a was used to arrange the first particles P1 on the resin substrate, and then the obtained filler 241b was used to arrange the second particles P2 on the resin substrate to form the particle layer 2. The concave-convex pattern 111a on the first substrate 11a was controlled so that the width k of the concaves was 6.0 μm, the pitch s of the convexities was 7.5 μm, and the height d of the convexities was 5.5 μm. The obtained electrode substrate 2 was used as Example 1.

[0215] <Method of manufacturing electrode substrate 3> As the fillers, the same fillers 241a and 241b as those used in forming the particle layer 2 on the electrode substrate 2 were used. The particle layer was formed by using method 2 shown in FIG. 20B. That is, the first particles P1 were arranged on the resin substrate using the above-mentioned filler 241a, and then the first particles P1 were rubbed with the particles S0. Thereafter, the second particles P2 were arranged on the resin substrate using the above-mentioned filler 241b, and the particle layer 3 was formed, thereby obtaining the electrode substrate 3. The obtained electrode substrate 3 was designated as Example 2.

[0216] <Method of manufacturing electrode substrate 4> As the fillers, the same fillers 241a and 241b as those used in forming the particle layer 2 on the electrode substrate 2 were used. The particle layer was prepared by using method 3 shown in FIG. 20C. That is, the first particles P1 were arranged on the resin substrate using the filler 241a, and then the first particles P1 were rubbed with the particles S0. Then, the second particles P2 were arranged on the resin substrate using the filler 241b. The first particles P1 and the second particles P2 were rubbed with the particles S0 using the rubbing unit of the particle layer forming unit U2 to form a particle layer 4, and an electrode substrate 4 was obtained. The obtained electrode substrate 4 was designated as Example 3.

[0217] <Method of manufacturing electrode substrate 5> As the fillers, the same fillers 241a and 241b as those used in forming the particle layer 2 on the electrode substrate 2 were used. The particle layer was formed by using the method 4 shown in FIG. 20D. That is, the first particles P1 were arranged on the resin substrate using the above-mentioned filler 241a, and then the first particles P1 were rubbed with the particles S0. Then, the second particles P2 were arranged on the resin substrate using the above-mentioned filler 241b. Then, the solid electrolyte particles P3 (LBO) were applied using the particle filling unit of the particle layer forming unit U2 to form a particle layer 5, and an electrode substrate 5 was obtained. The cumulative 50% particle diameter of the solid electrolyte particles P3 was 1.2 μm, which was smaller than the cumulative 50% particle diameter (11 μm) of the solid electrolyte particles P2. The obtained electrode substrate 5 was designated as Example 4.

[0218] <Method of Manufacturing Electrode Substrates 6 and 7> Particle layers 6 and 7 were formed under the same conditions as for the particle layer 3, except that the first particles P1 and the second particles P2 were changed as shown in Table 1, to obtain electrode substrates 6 and 7. The obtained electrode substrates 6 and 7 were designated as Examples 5 and 6.

[0219] <Method of Manufacturing Electrode Substrates 8 to 10> The arrangement pattern of the first particles P1 and the second particles P2 on the resin substrate was changed as shown in Table 1, and other conditions were the same as those for the particle layer 2 to form particle layers 8 to 10, thereby obtaining electrode substrates 8 to 10. The obtained electrode substrates 8 to 10 were designated as Examples 7 to 9. <Method of manufacturing electrode substrate 11> As the fillers, the same fillers 241a and 241b as those used in forming the particle layer 7 on the electrode substrate 7 were used. The particle layer was formed by using the method 4 shown in FIG. 20D. That is, the first particles P1 were arranged on the resin substrate using the above-mentioned filler 241a, and then the first particles P1 were rubbed with the particles S0. Then, the second particles P2 were arranged on the resin substrate using the above-mentioned filler 241b. Then, the solid electrolyte particles P3 (LBO) were applied using the particle filling unit of the particle layer forming unit U2 to form the particle layer 11, and the electrode substrate 11 was obtained. The cumulative 50% particle diameter of the solid electrolyte particles P3 was 1.2 μm, which was smaller than the cumulative 50% particle diameter (11 μm) of the solid electrolyte particles P2. The obtained electrode substrate 11 was used as Example 10.

[0220] In the manufacturing process of the electrode substrates 1 to 11, the compositions of the fillers 241a, 241b, and 241c used when forming a particle layer on a resin substrate using the particle layer forming unit U2, and The shape of the concave-convex pattern 111a on the base material 11a of No. 1 is shown in Tables 1 and 2. [Table 1] [Table 2] The support material S1 in the filler 241a, the support material S2 in the filler 241b, and the support material S3 in the filler 241c The support material S3 and the support material (particles S0) used for rubbing were all the standard carriers described above. In the table, the mass % of particles indicates the mass % of each particle in each filler.

[0221] Table 3 shows the particle size of the primary particles of each particle in the fillers 241a to c. The particle sizes shown in Table 3 are the particle sizes of the materials contained in the fillers before the particle layer is formed. The particle sizes (r10, r50, r90) of each particle are the particle sizes of the cumulative distribution in the volume-based particle size distribution of the primary particles, where r10 is the particle size at 10% cumulative, r50 is the particle size at 50% cumulative, and r90 is the particle size at 90% cumulative. In other words, r50 is the median size. The particle sizes were measured using a laser diffraction scattering type particle size distribution measuring device (LA-960 manufactured by Horiba, Ltd.). [Table 3] The standard carriers used as the support materials S1 to S3 and the rubbing particles had r10 of 60 μm, r50 of 81 μm, and r90 of 113 μm.

[0222] FIG. 22A is an SEM image of the upper side (the side on which the particle layer is formed) of the electrode substrate 2 of Example 1. Within the surface of the electrode substrate, LCO particles P1 are periodically dispersed and arranged. 22A and 22B, P1 indicates the active material particles of the electrode substrate, and P2 indicates the solid electrolyte particles of the electrode substrate.

[0223] 22B is a BIB-SEM image of a cross section of the electrode substrate 2 of Example 1. A particle layer including particles P1 and particles P2 was formed on the resin substrate (second substrate 11b) of the electrode substrate 2. In addition, in the particle layer, solid electrolyte particles LBO, which are particles P2, were arranged adjacent to LCO, which is particle P1. Particle P2 was arranged so as to cover a part of the surface of particle P1.

[0224] Table 4 shows the evaluation results of Comparative Example 1 and Examples 1 to 9. The evaluation methods will be described later. [Table 4] In the table, "coverage" refers to the coverage of the surface of the resin substrate by the active material particles and solid electrolyte particles. "Active material particle area ratio" refers to the area ratio of the exposed surface of the active material particle on the surface of the particle layer. "Upper surface" refers to the surface opposite to the side of the particle layer that contacts the resin substrate. "Lower surface" refers to the surface on the side of the particle layer that contacts the resin substrate. "Difference" refers to the difference between the area ratio of the exposed surface of the active material particle on the lower surface and the area ratio of the exposed surface of the active material particle on the upper surface.

[0225] The evaluation method of the electrode substrate and the calculation method of each index will be described below. <Coverage rate> The images for calculating the coverage were obtained by SEM observation. SEM observation was performed by photographing the upper surface of the electrode substrate (the side on which the particle layer was formed) from the vertical direction using an electron microscope (S-4800: manufactured by Hitachi, Ltd.). An example of the photographed SEM image is shown in FIG. 23A. The photographing was performed under the following conditions. Detector: ESB (backscattered electron beam) Observation conditions: Accelerating voltage 2 kV Magnification: 1000x Filter: ESB filter biased to 1500V

[0226] Next, the resin was analyzed using SEM-EDX (AMETEK PV77-47190ME). The elements and composition of each particle on the substrate were analyzed to distinguish between active material particles and solid electrolyte particles. In Fig. 23A, the active material particles are shown as white particles (P1) and the solid electrolyte particles are shown as gray particles (P2). The active material particles and the solid electrolyte particles are specifically identified by the following method. The resin substrate is analyzed by diffraction (XRD) to identify the materials that make up the resin substrate. Then, the specific elements contained in the active material particles and the solid electrolyte particles can be detected and identified by SEM-EDX. When LCO is used as the first particles P1, which are active material particles, and LBO is used as the second particles P2 and the third particles P3, which are solid electrolyte particles, the active material particles are identified by detecting Co by SEM-EDX, and the solid electrolyte particles are identified by detecting B by SEM-EDX.

[0227] The coverage rate was calculated by determining the ratio of the portion where particles are present across the entire screen of the SEM image obtained by the method described above. Specifically, it was calculated by the following image processing. OpenCV was used for image processing, and the analysis was performed in Python. The obtained SEM image was normalized so that the average brightness was 100 and the standard deviation was ±30. The normalized image was binarized with a threshold of brightness 50 to prepare an image in which all particles were represented by white pixels. An example of the prepared image is shown in Fig. 23B. The ratio represented by white pixels among all the pixels constituting the image was analyzed and calculated as the coverage rate of the particles. For example, the coverage rate in Fig. 23A is 97%.

[0228] <Imaging method of BIB-SEM> The calculation of the area ratio of the active material particles exposed on the surface of the particle layer was performed using BIB-SEM images. The imaging conditions of BIB-SEM are described below. Three resin substrates were laminated on a base (Al foil), and a sample prepared by vacuum packaging and isotropic pressure pressing was prepared. The sample was cut in the lamination direction with a wire saw (DWS3400 / wire diameter 170 μm · diamond diameter 30 μm), and the cross section was processed with a broad ion beam of Ar on the cut surface (JEOL SM-09010 Cross Section Polisher). The conditions for cross-section processing were a voltage of 6 kV and a current of 150 - 200 mA. As a BIB-SEM image, a cross section in the lamination direction of the resin substrate and the particle layer was obtained, and cross-section observation was performed.

[0229] The cross-section was photographed with an electron microscope (ULTRA55) under the following conditions. The imaging area was such that 5 images were taken from the central part of the cross-section, with 100 active material particles counted per image by the method described below, so that a total of 500 active material particles were counted. An example of the photographed image is shown in Fig. 24. Detector: ESB (reflected electron image) Observation conditions: acceleration voltage 3 kV Magnification: 1000 times Filter: Apply a bias of 1500 V to the ESB filter

[0230] Next, SEM-EDX (Bruker XFlash Detector 630M ) was used to perform elemental and compositional analysis of each particle on the resin substrate, and active material particles and solid electrolyte particles were distinguished from each other. The active material particles and solid electrolyte particles are identified by the method described above. The resin substrate is analyzed by X-ray diffraction (XRD) to identify the materials that make up the resin substrate. Then, the specific elements contained in the active material particles and solid electrolyte particles are detected and identified by SEM-EDX using the method described above.

[0231] <Method of calculating the area ratio of exposed active material particles on the surface of the particle layer> The active material particles and solid electrolyte particles were detected and identified from the BIB-SEM images taken under the above conditions. OpenCV was used for image processing, and analysis was performed using Python. The BIB-SEM images were normalized to an average brightness of 100 and a standard deviation of ±30. In order to count the active material particles on the resin substrate, an image showing only the particle layer on the resin substrate was cut out from the normalized image so as to include all particles in the particle layer. An example of an image cropped to include all the particles in the layer is shown in Figure 25A.

[0232] An image cut out from the normalized image so as to include all particles in the particle layer was binarized with a brightness threshold of 120 to obtain an image in which only the active material particles are represented by white pixels. For the purpose of noise removal, the area surrounded by the white pixels was filled with white, and then an opening process of the morphological transformation was performed with a kernel size of 3×3 pixels to obtain an image after noise removal. An example of an image after noise removal from an image in which only the active material particles are represented by white pixels is shown in FIG. 25B. FIG. 25B is an image of 55 vertical × 1024 horizontal pixels. Next, the image after noise removal was divided into columns of 1 pixel width. For example, in FIG. 25B, 1024 columns of 55 pixels vertical x 1 pixel horizontal were obtained. In each column of 1 pixel width after division, the top and bottom positions of the white pixels were determined. The top and bottom positions of the white pixels were recorded by determining the distance (number of pixels) from the bottom end of the column to the top and bottom of the white pixels. The obtained values ​​were designated as the value (P1-A) indicating the position of the top surface of the active material particles in each column, and the value (P1-B) indicating the position of the bottom surface of the active material particles.

[0233] Next, an image cut out from the normalized image so as to include all particles in the particle layer was binarized with a threshold brightness of 90 to obtain an image in which both the solid electrolyte particles and the active material particles are represented by white pixels. An example of an image in which both the solid electrolyte particles and the active material particles are represented by white pixels is shown in FIG. 25C. By subtracting the white pixel portion of the image in which only the active material particles are represented by white pixels from the image in which both the solid electrolyte particles and the active material particles are represented by white pixels, an image in which only the solid electrolyte particles are represented by white pixels is obtained. For the purpose of removing noise from the obtained image, the area surrounded by white pixels was filled with white, and then an opening process of the morphological transformation was performed with a kernel size of 3×3 pixels to obtain an image after removing noise. An example of the image after removing noise is shown in FIG. 25D. Next, the noise-removed image was divided into columns with a width of 1 pixel. In each column with a width of 1 pixel, the top and bottom positions of the white pixels were determined and recorded using the method described above. The obtained values ​​were taken as the position of the top surface of the solid electrolyte particles (P2-A) and the position of the bottom surface of the solid electrolyte particles (P2-B) in each column.

[0234] In each row, the value (P1-A) of the position of the top surface of the active material particles was compared with the value (P2-A) of the position of the top surface of the solid electrolyte particles. The number of rows in which the value (P1-A) of the position of the top surface of the active material particles was greater than the value (P2-A) of the position of the top surface of the solid electrolyte particles was recorded. That is, when the value (P1-A) of the position of the top surface of the active material particles was greater than the value (P2-A) of the top surface of the solid electrolyte particles, it was determined that the active material particles appeared on the top surface of the surface of the particle layer opposite to the side in contact with the resin substrate. As described above, each row is a row with a width of 1 pixel in the cross-sectional observation image of the particle layer. Therefore, the number of rows in which the value (P1-A) of the position of the top surface of the active material particles is greater than the value (P2-A) of the position of the top surface of the solid electrolyte particles can be considered to correspond to the number of pixels in which the active material particles appear on the top surface of the particle layer when the surface of the particle layer is observed from the vertical direction.

[0235] The ratio of the number of rows in which the value (P1-A) at the position of the top surface of the active material particles was greater than the value (P2-A) at the position of the top surface of the solid electrolyte particles was calculated relative to the total number of rows in the image. The obtained value was evaluated as the ratio of the exposed area of ​​the active material particles on the surface (upper surface) opposite to the side in contact with the resin substrate of the particle layer. Similarly, in each row of 1 pixel width, the value (P1-B) of the position of the bottom surface of the active material particles was compared with the value (P2-B) of the position of the bottom surface of the solid electrolyte particles. Then, the number of rows in which the value (P2-A) of the position of the bottom surface of the active material particles was smaller than the value (P2-B) of the position of the top surface of the solid electrolyte particles was recorded. In other words, when the value (P2-A) of the position of the bottom surface of the active material particles was smaller than the value (P2-B) of the position of the top surface of the solid electrolyte particles, it was determined that the active material particles were exposed on the top surface of the surface of the particle layer that contacts the resin substrate. The ratio of the number of rows in which the value (P1-B) at the position of the lowest surface of the active material particles was smaller than the value (P2-B) at the position of the lowest surface of the solid electrolyte particles to the total number of rows in the image was calculated. The obtained value was evaluated as the ratio of the exposed area of ​​the active material particles on the surface (lower surface) of the particle layer that contacts the resin substrate.

[0236] The difference between the area ratio of the exposed surface of the active material particles on the surface of the particle layer that comes into contact with the resin substrate, calculated by the above-mentioned method, and the area ratio of the exposed surface of the active material particles on the other surface of the particle layer, i.e., the surface opposite the side of the particle layer that comes into contact with the resin substrate, was determined. This treatment was performed on 103 active material particles observed on an SEM image of three particle layers of the same electrode substrate. Specifically, the above treatment was performed on each of the three particle layers shown in FIG.

[0237] From the above evaluation, a difference of 1% to 70% was judged as ◯, and a difference not satisfying 1% to 70% was judged as X. That is, in Table 4, a judgment of "◯" indicates that the difference between the proportion of active material particles appearing on the outermost surface on the surface of the particle layer in contact with the resin substrate and the proportion of active material particles appearing on the outermost surface on the surface opposite to the surface of the particle layer in contact with the resin substrate is 1 to 70 area %.

[0238] <Calculation method for average height of active material particles> From the BIB-SEM images taken under the above conditions, the active material particles and solid electrolyte particles were detected and identified by the above method. One layer of the image was cut out to include the resin substrate portion, and used as an image for calculating the average height of the active material particles. By the above method, an image (FIG. 25B) was obtained in which noise was removed from an image in which only the active material particles were represented by white pixels. The obtained image was divided into columns with a width of 1 pixel, and the position of the top surface of the active material particles (P1-A) was recorded by the above method. In the row where the active material particles were present, the difference (distance) from the upper surface of the resin substrate to P1-A was obtained, and the average value of the obtained values ​​was calculated. The length per pixel of the SEM image was calculated from the scale in the image, and the actual average height of the active material particles was calculated by multiplying the average by the above average. For example, in FIG. 25B, the length of one pixel is 0.11 μm, and the average value of the top surface of the active material particles is 40.3 pixels, so the average height of the active material particles was calculated to be 4.4 μm. The same process was performed on three SEM images in different fields of the same electrode substrate, and the overall average value was used as the average height of the active material particles from the resin substrate.

[0239] Electrodes (positive electrodes) were prepared from the electrode substrates of Examples 1 to 10, and all-solid-state batteries were assembled by the above-mentioned method. The results of evaluating the rate characteristics of all-solid-state batteries 1 to 10 produced using the electrode substrates of Examples 1 to 10 are shown below. The method for measuring the rate characteristics will be described later. [Table 5] In the table, "Air" indicates that sintering was performed in air, and "Ar-H2" indicates that sintering was performed in a reducing atmosphere (Ar-H2). In the rate characteristic evaluation of Examples 1 to 9 and Comparative Example 1, the actual capacity of each positive electrode active material was 120mAh / g for LCO, 130mAh / g for NMC, and 150mAh / g for LFP and LVP. The cutoff voltage was 4.2V / 2.6V for LCO, 4.2V / 2.6V for NMC, and 3.8V / 2.5V for LFP and LVP.

[0240] The method for evaluating the rate characteristics will be described below. <Rate characteristics> Mass of active material particles per unit area of ​​electrode substrate M (g / cm 2 ) to calculate the mass of the active material particles in the electrode (M × number of layers × electrode area (cm 2 )) to determine the current rate. The mass M of the active material particles per unit area is determined as follows. The weight of the first substrate 11a is measured after the first particles P1 are filled by the first filling device. Next, the weight of the first substrate 11a is measured after the particles P1 on the first substrate 11a are transferred to the second substrate 11b. The difference is measured and divided by the area of ​​the first substrate 11a (area of ​​the uneven region) to calculate. In the present disclosure, the active material particle mass M per unit area is calculated by the above method. Another calculation method is to use ICP emission spectroscopy. The active material particle mass per unit area M (g / cm) is calculated in advance by the above-mentioned method or the like. 2 Three levels of first base materials 11a with clear Co concentration are prepared. These first base materials 11a are dissolved by microwave acid decomposition (ETHOS PRO), and the acid decomposition solution is diluted with ultrapure water and subjected to ICP-AES measurement (CIROS CCD) to quantify the Co element. The active material particle mass per unit area M (g / cm) for the obtained element concentration is 2 From the calibration curve, the active material particle mass M (g / cm 2 ) can be obtained.

[0241] The actual capacity of the LCO was 120 mAh / g, and the cutoff voltage (vs. Li) was 4.2 V (charge) / 2.6 V (discharge). Using a charge / discharge device (manufactured by Biologic), charge / discharge measurements (constant current mode) were performed at each rate, and the capacity retention rate (discharge capacity / charge capacity x 100%) was measured. The maximum value R of the rate at which the capacity retention rate was 80% or higher was determined. Based on the maximum value R of the obtained rate, the rate characteristics were evaluated according to the following evaluation criteria. A:R≧0.3C B:0.3C>R When the rate characteristic evaluation was rated as A, it was determined that the electrode had excellent electronic conductivity and ionic conductivity and the internal resistance of the electrode was sufficiently suppressed. As a result, the rate characteristics were evaluated as A in Examples 1 to 9, confirming that the internal resistance of the electrode was sufficiently suppressed.

[0242] FIG. 26 is a BIB-SEM image of the cross section of an electrode manufactured using the electrode substrate 2 of Example 1. The substrate has been removed by sintering, and sintering of the particles has progressed. It is confirmed that the first particles P1, LCO, and the second particles P2, LBO, are arranged on the positive electrode current collector (Al foil) of the substrate 14, and that a large amount of LCO is in contact with the substrate 14. It is also confirmed that the same particles of both the LCO particles and the LBO particles are connected to each other in the z direction in the figure. This shows that electron and ion conduction can occur without interruption in the stacking direction, i.e., the z direction. Such a structure is realized by regularly arranging the particles on the electrode substrate, which is the electrode precursor.

[0243] 27A is a schematic diagram of an electrode substrate laminate produced by laminating the electrode substrate 1 of Example 1. For the sake of explanation, particles P1 and P2 are depicted as being spherical and having the same particle size. As described above, in the electrode substrate 1 of Example 1, the second solid electrolyte particles are in contact with the active material particles at a position opposite to the substrate side, forming a dense region. On the other hand, the surface area of ​​the active material particles P1 is exposed in large amounts on the substrate side, and is uniformly distributed. Even if the substrate is removed from the electrode substrate laminate by sintering, the particle arrangement structure of each substrate is maintained, and it is considered that a structure such as that shown in FIG. 27B is realized. Therefore, even in the electrode after the resin substrate is removed by sintering, the structure in which the particle layers are stacked is maintained, and in the thickness direction of the stacked particle layers, the active material particles that can effectively conduct electrons and the solid electrolyte particles that can effectively conduct ions are in contact with each other. Therefore, it is considered that both electronic conduction and ionic conduction are smoothly performed in the electrode created by stacking the electrode substrates, and the internal resistance can be suppressed.

[0244] In Examples 1 to 10, a laminate in which three sheets of the same positive electrode substrate were laminated was used, but a laminate in which multiple types of positive electrode substrates having the configuration of the present disclosure are laminated can also be used. In addition, the electrode substrate may be used as a material for a coating process (including a multilayer capacitor (MLCC) manufacturing technique) or a powder pressing process, which are conventionally known manufacturing methods.

[0245] The present disclosure relates to the following configurations and methods. (Configuration 1) An electrode substrate used in the manufacture of an electrode, The electrode substrate is A resin substrate, and active material particles and solid electrolyte particles on the resin substrate, a particle layer including the active material particles and the solid electrolyte particles is formed on the resin substrate; the solid electrolyte particles are arranged so as to cover at least a part of the surface of the active material particles when the particle layer is viewed through from the surface side in contact with the resin substrate or the surface side opposite to the surface in contact with the resin substrate, In cross-sectional observation of the particle layer using a scanning electron microscope (SEM), an area ratio of the exposed surface of the active material particles to a surface of the particle layer on the side in contact with the resin substrate; and An electrode substrate, wherein the difference between the area ratio of the exposed surface of the active material particles on the surface of the particle layer opposite to the side in contact with the resin substrate is 1 to 70 area %. (Configuration 2) The active material particles have an average height of 1 to 50 μm from the surface of the resin substrate. The electrode substrate according to claim 1. (Configuration 3) 3. The electrode substrate according to claim 1, wherein the difference is 5 to 60% by area. (Configuration 4) 3. The electrode substrate according to claim 1, wherein the difference is 10 to 50 area %. (Configuration 5) The solid electrolyte particles include at least one selected from the group consisting of Li-B oxide-based, Nasicon-type oxide-based, Perovskite-type oxide-based, and Garnet-type oxide-based electrolyte particles; 5. The electrode substrate according to any one of configurations 1 to 4, wherein the active material particles include Li-Co oxide-based active material particles. (Configuration 6) The solid electrolyte particles include at least one selected from the group consisting of Li-B oxide-based, Nasicon-type oxide-based, Perovskite-type oxide-based, and Garnet-type oxide-based electrolyte particles; 5. The electrode substrate according to any one of configurations 1 to 4, wherein the active material particles include Li-PO4 oxide-based active material particles. (Configuration 7) The solid electrolyte particles include at least one selected from the group consisting of Li-B oxide-based, Nasicon-type oxide-based, Perovskite-type oxide-based, and Garnet-type oxide-based electrolyte particles; 5. The electrode substrate according to any one of claims 1 to 4, wherein the active material particles include Si-based active material particles. (Configuration 8) The solid electrolyte particles include at least one selected from the group consisting of Li-B oxide-based, Nasicon-type oxide-based, Perovskite-type oxide-based, and Garnet-type oxide-based electrolyte particles; 5. The electrode substrate according to any one of configurations 1 to 4, wherein the active material particles include graphite-based active material particles. (Configuration 9) 9. The electrode base material according to any one of configurations 1 to 8, wherein a coverage rate of the surface of the resin base material with the active material particles and the solid electrolyte particles is 60% or more and 99% or less. (Configuration 10) An electrode substrate laminate comprising a plurality of electrode substrates according to any one of configurations 1 to 9 laminated together. (Configuration 11) 11. The electrode substrate laminate according to claim 10, the resin substrate and the particle layer are alternately arranged in a cross section of the electrode substrate laminate. (Configuration 12) 10. An electrode for a secondary battery, the electrode being a sintered body of the electrode base material according to any one of configurations 1 to 9. (Configuration 13) A sintered body of the electrode base material according to any one of configurations 1 to 9, The electrode is a sintered body obtained by removing at least a portion of the resin substrate in the electrode substrate. (Configuration 14) 14. A secondary battery comprising the electrode according to claim 12 or 13 and an electrolyte layer adjacent to the electrode. (Method 1) A method for producing an electrode base material according to any one of configurations 1 to 9, which is used in the production of an electrode, The production method comprises the steps of: preparing the resin substrate having an adhesive portion; disposing the active material particles on a surface of the adhesive portion; a step of rubbing the surfaces of the active material particles arranged on the surface of the adhesive portion with magnetic particles; disposing the solid electrolyte particles on the surface of the adhesion portion and the rubbed surfaces of the active material particles; A method for producing an electrode substrate having the above structure. (Method 2) A method for producing an electrode substrate used in the production of an electrode, comprising the steps of: The electrode substrate is A resin substrate, and active material particles and solid electrolyte particles on the resin substrate, a particle layer including the active material particles and the solid electrolyte particles is formed on the resin substrate; the solid electrolyte particles are arranged so as to cover at least a part of the surface of the active material particles when the particle layer is viewed through from the surface side in contact with the resin substrate or the surface side opposite to the surface in contact with the resin substrate, The production method comprises the steps of: preparing the resin substrate having an adhesive portion; disposing the active material particles on a surface of the adhesive portion; a step of rubbing the surfaces of the active material particles arranged on the surface of the adhesive portion with magnetic particles; disposing the solid electrolyte particles on the surface of the adhesive portion and the rubbed surfaces of the active material particles; A method for producing an electrode substrate having the above structure. (Method 3) The method for producing an electrode substrate according to Method 1 or 2, wherein the rubbing step includes a step of rubbing the surfaces of the active material particles with magnetic particles. (Method 4) A method for manufacturing an electrode, comprising the steps of: A step of laminating a plurality of electrode base materials according to any one of configurations 1 to 9 to form a laminate; removing the resin substrate from the laminate to obtain a three-dimensional object; and a step of pressing the three-dimensional object to obtain an electrode. (Method 5) A method for manufacturing a secondary battery, comprising: The production method comprises the steps of: Providing an electrode by the method for producing an electrode according to method 4; laminating the electrode, current collector and electrolyte; A method for manufacturing a secondary battery having the above structure. (Method 6) A method for manufacturing a secondary battery, comprising: The production method comprises the steps of: Providing an electrode by the method for producing an electrode according to method 4; and providing a solid electrolyte adjacent to the electrode. (Method 7) A method for manufacturing a secondary battery, comprising: A step of laminating a plurality of electrode base materials according to any one of configurations 1 to 9 to form a laminate; providing adjacent solid electrolytes on the laminate in a lump; removing the resin substrate from the laminate to obtain a three-dimensional object; Pressurizing the three-dimensional object; laminating a current collector on the pressed three-dimensional object; A method for manufacturing a secondary battery having the above structure.

Claims

1. An electrode substrate used in the manufacture of an electrode, The electrode substrate is A resin substrate, and active material particles and solid electrolyte particles on the resin substrate, a particle layer including the active material particles and the solid electrolyte particles is formed on the resin substrate; the solid electrolyte particles are arranged so as to cover at least a part of the surface of the active material particles when the particle layer is viewed through from the surface side in contact with the resin substrate or the surface side opposite to the surface in contact with the resin substrate, In a cross-sectional observation of the particle layer using a scanning electron microscope (SEM), an area ratio of the exposed surface of the active material particles to a surface of the particle layer on the side in contact with the resin substrate; and the difference between the area ratio of the exposed surface of the active material particles on the surface opposite to the side in contact with the resin substrate of the particle layer is 1 to 70 area %.

2. 2. The electrode substrate according to claim 1, wherein the active material particles have an average height from the surface of the resin substrate of 1 to 50 μm.

3. The electrode substrate according to claim 1, wherein the difference is 5 to 60 area %.

4. The electrode substrate according to claim 1, wherein the difference is 10 to 50 area %.

5. The solid electrolyte particles include at least one selected from the group consisting of Li-B oxide-based, Nasicon-type oxide-based, perovskite-type oxide-based, and garnet-type oxide-based electrolyte particles; The electrode substrate according to any one of claims 1 to 4, wherein the active material particles include Li-Co oxide-based active material particles.

6. The solid electrolyte particles include at least one selected from the group consisting of Li-B oxide-based, Nasicon-type oxide-based, perovskite-type oxide-based, and garnet-type oxide-based electrolyte particles; The active material particles are Li—PO 4 The electrode substrate according to any one of claims 1 to 4, comprising oxide-based active material particles.

7. The solid electrolyte particles include at least one selected from the group consisting of Li-B oxide-based, Nasicon-type oxide-based, perovskite-type oxide-based, and garnet-type oxide-based electrolyte particles; The electrode substrate according to any one of claims 1 to 4, wherein the active material particles include Si-based active material particles.

8. The solid electrolyte particles include at least one selected from the group consisting of Li-B oxide-based, Nasicon-type oxide-based, perovskite-type oxide-based, and garnet-type oxide-based electrolyte particles; The electrode substrate according to any one of claims 1 to 4, wherein the active material particles include graphite-based active material particles.

9. 5. The electrode substrate according to claim 1, wherein a coverage rate of the surface of the resin substrate with the active material particles and the solid electrolyte particles is 60% or more and 99% or less.

10. An electrode substrate laminate comprising a plurality of electrode substrates according to any one of claims 1 to 4 laminated together.

11. The electrode substrate laminate according to claim 10, the resin substrate and the particle layer are present alternately in a cross section of the electrode substrate laminate.

12. An electrode for a secondary battery, the electrode being a sintered body of the electrode base material according to any one of claims 1 to 4.

13. A sintered body of the electrode base material according to any one of claims 1 to 4, The electrode is a sintered body obtained by removing at least a portion of the resin substrate in the electrode substrate.

14. A secondary battery comprising the electrode of claim 12 and an electrolyte layer adjacent to the electrode.

15. A method for producing an electrode substrate according to any one of claims 1 to 4, which is used in the production of an electrode, The production method comprises: preparing the resin substrate having an adhesive portion; disposing the active material particles on a surface of the adhesive portion; a step of rubbing the surface of the active material particles arranged on the surface of the adhesive portion; disposing the solid electrolyte particles on the surface of the adhesion portion and the rubbed surfaces of the active material particles; A method for producing an electrode substrate having the above structure.

16. The method for producing an electrode substrate according to claim 15 , wherein the rubbing step includes a step of rubbing the surfaces of the active material particles with magnetic particles.

17. A method for producing an electrode substrate used in the production of an electrode, comprising the steps of: The electrode substrate is A resin substrate, and active material particles and solid electrolyte particles on the resin substrate, a particle layer including the active material particles and the solid electrolyte particles is formed on the resin substrate; the solid electrolyte particles are arranged so as to cover at least a part of the surface of the active material particles when the particle layer is viewed through from the surface side in contact with the resin substrate or the surface side opposite to the surface in contact with the resin substrate, The production method comprises: preparing the resin substrate having an adhesive portion; disposing the active material particles on a surface of the adhesive portion; a step of rubbing the surface of the active material particles disposed on the surface of the adhesive portion; disposing the solid electrolyte particles on the surface of the adhesive portion and the rubbed surfaces of the active material particles; A method for producing an electrode substrate having the above structure.

18. The method for producing an electrode substrate according to claim 17 , wherein the rubbing step includes a step of rubbing the surfaces of the active material particles with magnetic particles.

19. A method for manufacturing an electrode, comprising the steps of: A step of laminating a plurality of electrode base materials according to any one of claims 1 to 4 to form a laminate; removing the resin substrate from the laminate to obtain a three-dimensional object; and applying pressure to the three-dimensional object to obtain an electrode.

20. A method for manufacturing a secondary battery, comprising the steps of: The production method comprises: Providing an electrode by the method of claim 19; laminating the electrode, current collector and electrolyte; A method for manufacturing a secondary battery having the above structure.

21. A method for manufacturing a secondary battery, comprising the steps of: The production method comprises: Providing an electrode by the method of claim 19; and providing a solid electrolyte adjacent to the electrode.

22. A method for manufacturing a secondary battery, comprising the steps of: A step of laminating a plurality of electrode base materials according to any one of claims 1 to 4 to form a laminate; providing adjacent solid electrolytes on the laminate in a lump; removing the resin substrate from the laminate to obtain a three-dimensional object; Pressurizing the three-dimensional object; laminating a current collector on the pressed three-dimensional object; A method for manufacturing a secondary battery having the above structure.

Citation Information

Patent Citations

  • Method for producing material layer, method for producing stereo object, material layer, laminate, material layer forming apparatus, and lamination molding system

    JP2019137060A

  • Electrode applied to solid-state battery and solid-state battery

    JP2021039848A